ZnO-Al2O3-SiO2-based glass and method for producing same

By designing the composition and manufacturing process of ZnO-Al2O3-SiO2 series glass, the problem of rising lithium raw material prices after the popularization of lithium-ion batteries is solved, and a low-expanding material with excellent light transmission and thermal characteristics is provided to replace Li2O -Al2O3-SiO2-based crystallized glass, suitable for a variety of application scenarios.

CN119325457APending Publication Date: 2025-01-17NIPPON ELECTRIC GLASS CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202380045548.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-04-14
Filing Date
2023-06-02
Publication Date
2025-01-17

AI Technical Summary

Technical Problem

With the popularity of lithium-ion batteries and rising prices of lithium raw materials, it has become difficult to stabilize the manufacture of Li2O-Al2O3-SiO2-based crystalline glass, and a low-expanding material with excellent light transmittance and thermal characteristics can be replaced.

Method used

By designing the composition of ZnO-Al2O3-SiO2-type glass, it contains 40-90% SiO2, 5-35% Al2O3, 0-35% ZnO, 0-5% Li2O+Na2O+K2O, and during the manufacturing process, it is The melting and forming process is adopted, including overflow method, floating method, etc., and the linear thermal expansion coefficient is controlled below 60×10−7/℃, the light transmittance is above 0.1%, and the Young's modulus is above 65GPa.

Benefits of technology

It provides a ZnO-Al2O3-SiO2-type glass that can replace Li2O-Al2O3-SiO2-type crystallized glass, which has excellent light transmittance, heat resistance and heat impact resistance, and is suitable for cooking top plates, fireproof windows and buildings. Use materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005174647230000371
    Figure BDA0005174647230000371
  • Figure BDA0005174647230000381
    Figure BDA0005174647230000381
  • Figure BDA0005174647230000391
    Figure BDA0005174647230000391
Patent Text Reader

Abstract

Provided is a glass which can replace a Li2O-Al2O3-SiO2-based crystallized glass and has excellent light transmittance, heat resistance, and thermal shock resistance. The ZnO-Al2O3-SiO2-based glass according to the present invention is characterized by containing, in mass%, 40 to 90% of SiO2, 5 to 35% of Al2O3, more than 0% but not more than 35% of ZnO, and 0 to 5% of Li2O + Na2O + K2O.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a ZnO-Al2O3-SiO2 system glass and a ZnO-Al2O3-SiO2 system crystallized glass having low thermal expansion characteristics. Background Art

[0002] In the past, crystallized glass was used as a material for front windows of oil stoves, wood stoves, etc., fixtures for burning electronic parts, furnace core tubes for semiconductor manufacturing, components for dimensional measurement, components for communication, building materials, containers for chemical reactions, top plates for electromagnetic cooking, heat-resistant tableware, heat-resistant covers, window glass for fireproof doors, components for astronomical telescopes, linear thermal expansion coefficient adjustment components, etc. For example, in patent documents 1 to 3, a crystallized glass formed by crystallization of Li2O-Al2O3-SiO2 system such as β-quartz solid solution (Li2O·Al2O3·nSiO2, wherein 2≤n≤4) or β-spodumene solid solution (Li2O·Al2O3·nSiO2, wherein n≥4) is disclosed as the main crystal.

[0003] This crystallized glass has excellent thermal properties because its linear thermal expansion coefficient is low and its mechanical strength is also high. In addition, by appropriately adjusting the heat treatment conditions in the crystallization process, the type of crystallization can be controlled, thereby the crystallized glass with light transmittance can be easily made.

[0004] Prior art literature

[0005] Patent Literature

[0006] Patent Document 1: Japanese Patent Publication No. 39-21049

[0007] Patent Document 2: Japanese Patent Publication No. 40-20182

[0008] Patent Document 3: Japanese Patent Application Laid-Open No. 1-308845 Summary of the invention

[0009] Technical problem to be solved by the invention

[0010] On the other hand, in recent years, with the popularization of lithium-ion batteries, the price of lithium raw materials has risen, and it has become increasingly difficult to stably manufacture Li2O-Al2O3-SiO2-based crystallized glass and supply it to the market.

[0011] Based on this background, there is a need for a low expansion material that is light-transmissive and has excellent thermal properties and can replace Li2O-Al2O3-SiO2-based crystallized glass.

[0012] The object of the present invention is to provide a ZnO-Al2O3-SiO2 glass having excellent light transmittance and thermal properties, especially heat resistance and thermal shock resistance, which can replace Li2O-Al2O3-SiO2 crystallized glass.

[0013] Technical solutions for solving technical problems

[0014] The inventors of the present invention have found through intensive research that by appropriately designing the glass composition, a low thermal expansion glass having a low linear thermal expansion coefficient and excellent light transmittance, heat resistance and thermal shock resistance can be obtained. In addition, in the present invention, ZnO-Al2O3-SiO2 glass is treated as a composition whose main components are ZnO, Al2O3 and SiO2.

[0015] The ZnO-Al2O3-SiO2 glass of the present invention is characterized in that, in terms of mass %, it contains 40 to 90% SiO2, 5 to 35% Al2O3, more than 0% and less than 35% ZnO, and 0 to 5% Li2O+Na2O+K2O.

[0016] The ZnO-Al2O3-SiO2 glass of the present invention preferably contains more than 0% of Fe2O3 in terms of mass%.

[0017] The ZnO-Al2O3-SiO2 glass of the present invention preferably contains 10% by mass or less of HfO2.

[0018] The ZnO-Al2O3-SiO2 glass of the present invention preferably contains 30 ppm or less of Pt and 30 ppm or less of Rh.

[0019] The ZnO-Al2O3-SiO2 glass of the present invention preferably contains more than 0% of MoO3 in terms of mass%.

[0020] The ZnO-Al2O3-SiO2 glass of the present invention preferably contains more than 0% SnO2 in terms of mass%.

[0021] The ZnO-Al2O3-SiO2 glass of the present invention preferably contains more than 0% of Cr2O3 in terms of mass%.

[0022] The ZnO-Al2O3-SiO2 glass of the present invention preferably contains Al2O3 / ZnO in a mass ratio of 0.14 to 2300.

[0023] The ZnO-Al2O3-SiO2 glass of the present invention preferably has a mass ratio of ZnO / (SiO2+B2O3) exceeding 0 and being equal to or less than 0.75.

[0024] The ZnO-Al2O3-SiO2 glass of the present invention preferably has a mass ratio of (Li2O+Na2O+K2O) / Fe2O3 of 10,000 or less.

[0025] The ZnO-Al2O3-SiO2 glass of the present invention preferably contains, in mass %, ZnO+B2O3+P2O5 exceeding 0 and being 55% or less.

[0026] The ZnO-Al2O3-SiO2 glass of the present invention preferably has a mass ratio of (ZnO+B2O3+P2O5) / ZnO of 1.001 or more.

[0027] The ZnO-Al2O3-SiO2 glass of the present invention preferably has a linear thermal expansion coefficient of 60×10 ﹣7 / ℃ below.

[0028] The ZnO-Al2O3-SiO2 glass of the present invention preferably has a light transmittance of 0.1% or more at a thickness of 4 mm and a wavelength of 555 nm.

[0029] The ZnO-Al2O3-SiO2 glass of the present invention preferably has a Young's modulus of 65 GPa or more.

[0030] ZnO-Al2O3-SiO2 system glass of the present invention can be crystallized glass. In addition, in the present invention, when ZnO-Al2O3-SiO2 system glass is crystallized glass, this crystallized glass is sometimes referred to as "ZnO-Al2O3-SiO2 system crystallized glass".

[0031] The manufacturing method of the ZnO-Al2O3-SiO2 glass of the present invention is used to manufacture any of the above-mentioned glasses, and the method is characterized in that it includes: a step of melting glass raw materials to obtain molten glass; and a step of shaping the above-mentioned molten glass, and the method for shaping the above-mentioned molten glass is selected from at least one of the overflow method, the floating method, the down-drawing method, the flow hole down-drawing method, the re-dragging method, the containerless method, the blowing method, the pressing method, the rolling method, the bushing method and the tube drawing method.

[0032] The method for producing the ZnO-Al2O3-SiO2-based glass of the present invention may further include a step of crystallizing the glass obtained by the step of shaping the molten glass.

[0033] The ZnO-Al2O3-SiO2 glass of the present invention is preferably used for a top plate for a cooker, a fireproof window, a heat-resistant tableware or a building material.

[0034] Effects of the Invention

[0035] According to the present invention, it is possible to provide a ZnO-Al2O3-SiO2 system glass having excellent light transmittance, heat resistance and thermal shock resistance, which can replace the Li2O-Al2O3-SiO2 system crystallized glass. DETAILED DESCRIPTION

[0036] The ZnO-Al2O3-SiO2 glass of the present invention (hereinafter also referred to as "glass") is characterized by containing, by mass%, 40 to 90% of SiO2, 5 to 35% of Al2O3, more than 0% and less than 35% of ZnO, and 0 to 5% of Li2O+Na2O+K2O. The reasons for setting the content and characteristics of each component as described above are explained below. In addition, in the following description of the content of each component, "%" means "mass %" unless otherwise specified.

[0037] SiO2 is a component that forms the glass skeleton. Moreover, it is a component that particularly affects the ease of phase separation. The SiO2 content is 40-90%, preferably 50-90%, 45-85%, 40-82%, 41-80%, 50-80%, 52%-79%, 53%-78%, 53.5-77%, and particularly preferably 54-76%. When the SiO2 content is too little, there is a tendency for the linear thermal expansion coefficient to increase, and it is difficult to obtain glass with excellent heat resistance and thermal shock resistance. Moreover, there is also a tendency for chemical durability to decrease. On the other hand, when the SiO2 content is too much, the homogeneity of the glass melt is easily reduced. Moreover, scum with a high SiO2 content is easily generated on the surface of the glass melt, and devitrified materials such as cristobalite are precipitated from the scum, which is easy to increase the manufacturing load.

[0038] Al2O3 is a component that forms the skeleton of glass. Moreover, Al2O3 is also a component that affects the ease of phase separation. The Al2O3 content is 5-35%, preferably 7-33%, 9-30%, 10-28%, and particularly preferably 11-25%. When the Al2O3 content is too little, there is a tendency for the linear thermal expansion coefficient to increase, and it is difficult to obtain glass with excellent heat resistance and thermal shock resistance. In addition, the chemical durability is reduced, and the glass surface is prone to deterioration. As a result, the state of the surface unevenness deteriorates, and it is difficult to obtain the desired light transmittance. On the other hand, when the Al2O3 content is too much, the homogeneity of the glass melt is easily reduced. In addition, there is a tendency for crystals such as mullite to precipitate and cause the glass to lose transparency, and the glass is easily broken.

[0039] ZnO is a component that reduces the viscosity of glass and improves the meltability and formability of glass. It is also a component used to adjust the linear thermal expansion coefficient and refractive index of glass. It is also a component that affects the phase separation of glass and a constituent component of Zn-containing crystals such as ZnAl2O4 (zinc spinel). The ZnO content is more than 0% and less than 35%, preferably 1-35%, 3-35%, 5-35%, 7-35%, 9-35%, 9-32%, 9-28%, 9-25%, 9-23%, and particularly preferably 9-21%. When the ZnO content is too low, there is a tendency for crystals such as mullite to precipitate and cause the glass to lose clarity. In addition, the homogeneity of the glass melt is easily reduced. On the other hand, when the ZnO content is too high, the linear thermal expansion coefficient becomes too large, and it is difficult to obtain glass with excellent heat resistance and thermal shock resistance. In addition, the homogeneity of the glass melt is easily reduced. In addition, the chemical durability of the glass is reduced, and the glass surface is easily deteriorated. As a result, the state of surface irregularities deteriorates, making it difficult to obtain desired light transmittance.

[0040] Zn cations, Al cations, and O anions are sometimes coordinated in the form of charge compensation in glass and crystallized glass. Therefore, when electrically neutral coordination is formed and chemical bonds with high covalent bonding are formed, chemical stability is particularly easy to achieve. Glass with a chemically stable coordination structure has excellent chemical resistance and high thermal shock resistance. Therefore, in terms of mass ratio, Al2O3 / ZnO (the value obtained by dividing the Al2O3 content by the ZnO content) is preferably 0.14-2300, 0.14-1000, 0.14-500, 0.1-100, 0.1-100, 0.14-4.5, 0.14-4, 0.14-3.5, 0.14-3, 0.14-2.5, 0.14-2, 0.3-2, 0.5-2, 0.6-2, 0.6-1.9, and particularly preferably 0.7-1.9.

[0041] Li2O, Na2O, and K2O are components that reduce the viscosity of glass and improve the solubility and formability of glass. Moreover, they are components that affect the phase separation of glass. Li2O+Na2O+K2O (the total amount of Li2O, Na2O, and K2O) is 0-5%, preferably 0-4.5%, 0-4%, 0-3.5%, 0-3%, 0-2.5%, 0-2%, 0-1.5%, 0-1%, 0-0.9%, 0-0.8%, 0-0.7%, 0-0.6%, 0-0.5%, 0-0.4%, 0-0.35%, 0-0.3%, 0-0.2%, 0-0.1%, and particularly preferably 0-0.05%. When there is too much Li2O+Na2O+K2O, the linear thermal expansion coefficient becomes too large, and it is difficult to obtain glass with excellent heat resistance and thermal shock resistance. Moreover, the homogeneity of the glass melt is easily reduced. Moreover, the chemical durability of the glass is reduced, and the glass surface is easily deteriorated. As a result, the state of the surface roughness deteriorates, and it is difficult to obtain the desired light transmittance. In addition, since Li2O, Na2O, and K2O are easily mixed as impurities, if you want to completely remove them, there is a tendency that the raw material batch price becomes higher and the manufacturing cost increases. In the case of suppressing the increase in manufacturing cost, the lower limit of the content of Li2O+Na2O+K2O is preferably more than 0%, more than 0.0001%, more than 0.0003%, more than 0.0005%, and particularly preferably more than 0.001%.

[0042] Li2O is a component that reduces the viscosity of glass and improves the meltability and formability of glass. Moreover, it is a component that affects the phase separation of glass. The Li2O content is preferably 0-5%, 0-4.5%, 0-4%, 0-3.5%, 0-3%, 0-2.5%, 0-2%, 0-1.5%, 0-1%, 0-0.9%, 0-0.8%, 0-0.7%, 0-0.6%, 0-0.5%, 0-0.4%, and particularly preferably 0-0.39%. When the Li2O content is too much, the linear thermal expansion coefficient becomes too large, and it is difficult to obtain glass with excellent heat resistance and thermal shock resistance. In addition, the homogeneity of the glass melt is easily reduced. In addition, the chemical durability of the glass is reduced, and the glass surface is easily deteriorated. As a result, the state of the surface concave and convex becomes worse, and it is difficult to obtain the desired light transmittance. In addition, since Li2O is easily mixed as an impurity, if Li2O is to be completely removed, there is a tendency that the raw material batch price changes and the manufacturing cost increases. Therefore, in the case of suppressing the increase in manufacturing cost, the lower limit of the Li2O content is preferably more than 0%, 0.0001% or more, 0.0002% or more, 0.0003% or more, 0.0004% or more, 0.0005% or more, and particularly preferably 0.001% or more.

[0043] Na2O is a component that reduces the viscosity of glass and improves the meltability and formability of glass. It is also a component used to adjust the linear thermal expansion coefficient and refractive index of low thermal expansion glass, and is also a component that affects the phase separation of glass. The Na2O content is preferably 0-5%, 0-4.5%, 0-4%, 0-3.5%, 0-3%, 0-2.5%, 0-2%, 0-1.5%, 0-1%, 0-0.9%, 0-0.8%, 0-0.7%, 0-0.6%, 0-0.5%, 0-0.4%, and is particularly preferably 0-0.39%. When the Na2O content is too much, the linear thermal expansion coefficient becomes too large, and it is difficult to obtain glass with excellent heat resistance and thermal shock resistance. In addition, the homogeneity of the glass melt is easily reduced. In addition, the chemical durability of the glass is reduced, and the glass surface is easily deteriorated. As a result, the state of the surface concave and convex becomes worse, and it is difficult to obtain the desired light transmittance. In addition, since Na2O is easily mixed as an impurity, if Na2O is to be completely removed, there is a trend that the raw material batch price becomes high and the manufacturing cost increases. Therefore, in the case of suppressing the increase in manufacturing cost, the lower limit of Na2O content is preferably more than 0%, more than 0.0001%, more than 0.0003%, more than 0.0005%, more than 0.001%, more than 0.002%, more than 0.004%, more than 0.006%, more than 0.008%, and particularly preferably more than 0.01%.

[0044] K2O is a component that reduces the viscosity of glass and improves the meltability and formability of glass. In addition, it is a component used to adjust the linear thermal expansion coefficient and refractive index of low thermal expansion glass, and is also a component that affects the phase separation of glass. The K2O content is preferably 0-5%, 0-4.5%, 0-4%, 0-3.5%, 0-3%, 0-2.5%, 0-2%, 0-1.5%, 0-1%, 0-0.9%, 0-0.8%, 0-0.7%, 0-0.6%, 0-0.5%, 0-0.4%, and particularly preferably 0-0.39%. When the K2O content is too much, the linear thermal expansion coefficient becomes too large, and it is difficult to obtain glass with excellent heat resistance and thermal shock resistance. In addition, the homogeneity of the glass melt is easily reduced. In addition, the chemical durability of the glass is reduced, and the glass surface is easily deteriorated. As a result, the state of the surface concave and convex becomes worse, and it is difficult to obtain the desired light transmittance. In addition, since K2O is easily mixed as an impurity, if K2O is to be completely removed, the raw material batch price becomes expensive and the manufacturing cost tends to increase. Therefore, in order to suppress the increase in manufacturing cost, the lower limit of the K2O content is preferably more than 0%, 0.0001% or more, 0.0003% or more, 0.0005% or more, and particularly preferably 0.001% or more.

[0045] The ZnO-Al2O3-SiO2 system glass of the present invention may contain the following components in addition to the above-mentioned components.

[0046] Fe2O3 is a component that reduces the viscosity of glass and improves the melting and forming properties of glass by containing it in an appropriate amount. It is also a component that releases oxygen-based gases through redox reactions and affects the clarity of glass. It is also a coloring component of glass that absorbs light of various wavelengths and a component that affects the phase separation of glass. The Fe2O3 content is preferably more than 0%, more than 0.0001%, more than 0.0003%, more than 0.0005%, more than 0.0007%, more than 0.0009%, more than 0.0011%, more than 0.0013%, more than 0.0015%, more than 0.002%, more than 0.003%, more than 0.004%, more than 0.005%, more than 0.006%, more than 0.007%, more than 0.008%, more than 0.009%, and particularly preferably more than 0.01%. On the other hand, when the Fe2O3 content is too much, the glass is easily colored and it is difficult to obtain the desired light transmittance. In addition, Fe-containing devitrified materials are easily precipitated, increasing the manufacturing load. Therefore, the Fe2O3 content is preferably less than 20%, less than 15%, less than 10%, less than 5%, less than 1%, less than 0.5%, and particularly preferably less than 0.1%. In addition, the Fe2O3 content can also be controlled to adjust the light transmittance according to the use of the glass of the present invention. For example, in the case where a colored (e.g., black) appearance is required in a cooking top plate, the Fe2O3 content can be more than 0.05%, more than 0.08%, more than 0.1%, more than 0.2%, and particularly more than 0.3%.

[0047] Li2O, Na2O, and K2O are components that reduce the viscosity of the glass and improve the solubility and formability of the glass, respectively. In addition, they affect the optical basicity of the glass. The greater the amount of Li2O, Na2O, and K2O, the higher the optical basicity tends to be. On the other hand, Fe2O3 is a coloring component of the glass that absorbs light of various wavelengths. When the optical basicity of the glass is high, Fe ions tend to exist in the glass as trivalent, and when the optical basicity of the glass is low, Fe ions tend to exist as divalent. Trivalent Fe ions tend to absorb light from the ultraviolet region to the visible light region, and divalent Fe ions tend to absorb light in the infrared region. According to the use of the glass of the present invention, it is necessary to adjust the light transmittance in the ultraviolet region, the visible light region, and the infrared region, and it is preferred to appropriately control the optical basicity of the glass and the valence of the Fe ions. Therefore, (Li2O+Na2O+K2O) / Fe2O3 (the value obtained by dividing the total amount of Li2O, Na2O, and K2O by the Fe2O3 content) is preferably greater than 0, greater than 0.1, greater than 0.2, greater than 0.3, greater than 0.4, and particularly preferably greater than 0.5. By setting in this way, it is easy to reduce the viscosity of the glass and adjust the light transmittance in the ultraviolet region, the visible light region, and the infrared region. In addition, (Li2O+Na2O+K2O) / Fe2O3 is preferably less than 10000, less than 1000, less than 100, less than 50, less than 40, less than 30, less than 25, and particularly preferably less than 15. By setting in this way, the viscosity of the glass will not be excessively reduced and it is easy to form.

[0048] HfO2 is a component that improves the Young's modulus and rigidity modulus of glass, and is also a component that reduces the viscosity of glass and improves the meltability and formability of glass. And it is a component that can affect the phase separation of glass. In addition, it is necessary to control the HfO2 content according to the use of the glass of the present invention, and design it in a way that the required strength can be obtained. When the HfO2 content is too much, the mechanical strength of the glass or crystallized glass becomes too high, and it is difficult to process, etc., and it is difficult to obtain the required surface state and the required excellent light transmittance. In addition, due to the high price of HfO2 raw materials, the manufacturing cost increases. According to the above situation, HfO2 content is preferably less than 10%, less than 9%, less than 8%, less than 7%, less than 6%, less than 5%, less than 4%, less than 3%, less than 2%, less than 1%, less than 0.5%, less than 0.4%, less than 0.3%, and particularly preferably less than 0.2%. In addition, the lower limit of HfO2 content is not particularly limited, and is more than 0%, but HfO2 is a component that can be mixed from the raw materials used, and its mixing amount varies according to the raw material composition. Therefore, in reality, HfO 2 may be contained in an amount of 0.0001% or more, 0.0003% or more, and particularly 0.0005% or more.

[0049] Pt is a component that can be mixed into the glass in the form of ions, colloids, metals, etc., and exhibits yellow to brown coloring. In addition, it is a component that affects the phase separation of the glass. The Pt content is preferably 30ppm or less, 28ppm or less, 26ppm or less, 24ppm or less, 22ppm or less, 20ppm or less, 18ppm or less, 16ppm or less, 14ppm or less, 12ppm or less, 10ppm or less, 8ppm or less, 6ppm or less, 4ppm or less, 2ppm or less, 1.6ppm or less, 1.4ppm or less, 1.2ppm or less, 1ppm or less, 0.9ppm or less, 0.8ppm or less, 0.7ppm or less, 0.6ppm or less, 0.5ppm or less, 0.45ppm or less, 0.4ppm or less, 0.35ppm or less, and particularly preferably 0.3ppm or less. When the Pt content is too much, devitrified materials containing Pt are easily precipitated, increasing the manufacturing load. In addition, the lower limit of Pt content is not particularly limited, and may be 0ppm, but in the case of using conventional melting equipment, in order to obtain homogeneous glass, it is sometimes necessary to use Pt parts. Therefore, if Pt is completely removed, there is a trend of increased manufacturing costs. In the case of not causing adverse effects on coloring, in order to suppress the increase in manufacturing costs, the lower limit of Pt content is preferably 0.0001ppm or more, 0.001ppm or more, 0.005ppm or more, 0.01ppm or more, 0.03ppm or more, 0.05ppm or more, particularly preferably 0.07ppm or more.

[0050] Rh is a component that can be mixed into the glass in the form of ions, colloids, metals, etc., and exhibits yellow to brown coloration. Moreover, it is a component that affects the phase separation of the glass. The Rh content is preferably 30ppm or less, 28ppm or less, 26ppm or less, 24ppm or less, 22ppm or less, 20ppm or less, 18ppm or less, 16ppm or less, 14ppm or less, 12ppm or less, 10ppm or less, 8ppm or less, 6ppm or less, 4ppm or less, 2ppm or less, 1.6ppm or less, 1.4ppm or less, 1.2ppm or less, 1ppm or less, 0.9ppm or less, 0.8ppm or less, 0.7ppm or less, 0.5ppm or less, 0.4ppm or less, 0.35ppm or less, and particularly preferably 0.3ppm or less. When the Rh content is too much, it is easy to precipitate a devitrified material containing Rh, increasing the manufacturing load. In addition, the lower limit of the Rh content is not particularly limited, and can be 0ppm, but in the case of using conventional melting equipment, in order to obtain homogeneous glass, it is sometimes necessary to use Rh components. Therefore, if Rh is to be completely removed, there is a tendency for the manufacturing cost to increase. In order to suppress the increase in manufacturing cost without causing adverse effects on coloration, the lower limit of the Rh content is preferably 0.0001 ppm or more, 0.001 ppm or more, 0.005 ppm or more, 0.01 ppm or more, 0.03 ppm or more, 0.04 ppm or more, 0.05 ppm or more, and particularly preferably 0.07 ppm or more.

[0051] In addition, Pt+Rh (the total amount of Pt and Rh) is preferably 60 ppm or less, 56 ppm or less, 52 ppm or less, 48 ​​ppm or less, 44 ppm or less, 42 ppm or less, 38 ppm or less, 34 ppm or less, 30 ppm or less, 26 ppm or less, 22 ppm or less, 18 ppm or less, 14 ppm or less, 10 ppm or less, 6 ppm or less, 4.5 ppm, 4 ppm or less, 3.75 ppm or less, 3.5 ppm or less, 3 ppm or less, 2.75 ppm or less, 2.5 ppm or less, 2.25 ppm or less, 2 ppm or less, 1.75 ppm or less, 1.25 ppm or less, 1 ppm or less, 0.9 ppm or less, 0.8 ppm or less, 0.7 ppm or less, 0.6 ppm or less, 0.5 ppm or less, 0.4 ppm or less, and particularly preferably 0.3 ppm or less. In addition, the lower limit of Pt+Rh is not particularly limited, and can be 0ppm, but in the case of using conventional melting equipment, in order to obtain homogeneous glass, it is sometimes necessary to use Pt parts and / or Rh parts. Therefore, if you want to completely remove Pt and Rh, there is a trend of increased manufacturing costs. In the case of not causing adverse effects on coloring, in order to suppress the increase in manufacturing costs, the lower limit of Pt+Rh is preferably more than 0.0001ppm, more than 0.001ppm, more than 0.005ppm, more than 0.01ppm, more than 0.03ppm, more than 0.05ppm, and particularly preferably more than 0.07ppm.

[0052] MoO3 is a component that reduces the viscosity of glass and improves the meltability and formability of glass by containing it in an appropriate amount. Moreover, it is also a coloring component of glass that absorbs light of various wavelengths. Moreover, it is a component that affects the phase separation of glass. The MoO3 content is preferably more than 0%, and particularly preferably more than 0.0001%. On the other hand, when the MoO3 content is too much, the glass is easily colored and it is difficult to obtain the required light transmittance. Moreover, it is easy to precipitate Mo-containing devitrified materials, increasing the manufacturing load. Therefore, the MoO3 content is preferably less than 20%, less than 15%, less than 10%, less than 5%, less than 1%, less than 0.5%, and particularly preferably less than 0.1%. In addition, the MoO3 content can also be controlled according to the use of the glass of the present invention to adjust the light transmittance. For example, when a colored appearance is required in a cooking top plate, the MoO3 content can be set to more than 0.01%, more than 0.05%, more than 0.08%, more than 0.1%, more than 0.2%, and particularly more than 0.3%.

[0053] SnO2 is a component that acts as a clarifier. In addition, it is also a component used to adjust the linear thermal expansion coefficient and refractive index of glass or crystallized glass. Moreover, it is also a component that affects the phase separation of glass. The SnO2 content is preferably 0% or more, more than 0%, more than 0.0001%, more than 0.001%, more than 0.005%, more than 0.01%, more than 0.03%, more than 0.05%, more than 0.1%, more than 0.15%, and particularly preferably more than 0.2%. When the SnO2 content is too much, the linear thermal expansion coefficient becomes too large, and it is difficult to obtain glass with excellent heat resistance and thermal shock resistance. Moreover, it is easy to reduce the homogeneity of the glass melt. In addition, the chemical durability of the glass is reduced, and the glass surface is easily deteriorated. As a result, the state of the surface concave and convex becomes worse, and it is difficult to obtain the desired light transmittance. The upper limit of the SnO2 content is not particularly limited, and it is 20% in reality. When the content exceeds 20%, it is easy to precipitate Sn-containing devitrified materials, increasing the manufacturing load.

[0054] Cr2O3 is a component that reduces the viscosity of glass and improves the meltability and formability of glass by containing it in an appropriate amount. It is also a coloring component of glass that absorbs light of various wavelengths. Moreover, it is a component that affects the phase separation of glass. The Cr2O3 content is preferably more than 0%, more than 0.00001%, more than 0.00005%, more than 0.0001%, and particularly preferably more than 0.0005%. On the other hand, when the Cr2O3 content is too much, it is easy to precipitate devitrified materials containing Cr, increasing the manufacturing load. In addition, the glass is easily colored and it is difficult to obtain the desired light transmittance. Therefore, the Cr2O3 content is preferably less than 20%, less than 15%, less than 10%, less than 5%, less than 1%, less than 0.5%, and particularly preferably less than 0.1%. In addition, according to the use of the glass of the present invention, the Cr2O3 content can be controlled to adjust the light transmittance. For example, when a colored appearance is required in a cooking top plate, in addition to the preferred range mentioned above, it can also be set to 0.01% or more, 0.05% or more, 0.08% or more, 0.1% or more, 0.15% or more, 0.18% or more, 0.2% or more, 0.25% or more, 0.3% or more, 0.4% or more, 0.5% or more, 0.6% or more, among which 0.7% or more is particularly preferred.

[0055] B2O3 is a component that reduces the viscosity of glass and improves the meltability and formability of glass. Moreover, it is a component that particularly affects the ease of phase separation. The B2O3 content is preferably 0-30%, more than 0% and less than 30%, more than 0% and less than 25%, 1-25%, 2-20%, 2.5-19%, 3-18%, 3.5-17%, 4-16%, and particularly preferably 4.5-15%. When the B2O3 content is too much, the evaporation amount of B2O3 during melting increases, and scum with relatively less B2O3 content and relatively more SiO2 content is easily generated on the surface of the glass melt. As a result, devitrified materials such as cristobalite are easily precipitated from the scum, increasing the manufacturing load. In addition, the chemical durability of the glass is reduced, and the glass surface is easily deteriorated, thereby worsening the surface concave-convex state and making it difficult to obtain the desired light transmittance.

[0056] ZnO, SiO2, and B2O3 are components that affect the ease with which glass phase separation occurs. By appropriately controlling the content ratio of these components, phase separation due to binodal decomposition is easily exhibited, and as a result, the desired light transmittance is easily obtained. In addition, the reason why the desired light transmittance is easily obtained when phase separation due to binodal decomposition is exhibited will be described later. ZnO / (SiO2+B2O3) (the value obtained by dividing the ZnO content by the total amount of SiO2 and B2O3) is preferably greater than 0 and less than 0.75, greater than 0 and less than 0.7, greater than 0 and less than 0.65, greater than 0 and less than 0.6, 0.05 to 0.6, and particularly preferably 0.1 to 0.6.

[0057] MgO is a component that reduces the viscosity of glass and improves the meltability and formability of glass. It is also a component used to reduce the linear thermal expansion coefficient of low thermal expansion glass and adjust the refractive index. It is also a component that affects the phase separation of glass. The MgO content is preferably 0-30%, 0-25%, 0-20%, 0-15%, 0-10%, 0-9%, 0-8%, 0-7%, 0-6%, 0-5%, 0-4%, 0-3%, 0-2%, 0-1.5%, 0-1%, 0-0.5%, 0-0.25%, and particularly preferably 0-0.1%. When the MgO content is too much, the linear thermal expansion coefficient becomes too large, and it is difficult to obtain glass with excellent heat resistance and thermal shock resistance. In addition, the chemical durability of the glass is reduced, and the glass surface is easily deteriorated. As a result, the state of the surface concave and convex becomes worse, and it is difficult to obtain the desired light transmittance. In addition, since MgO is easily mixed as an impurity, if MgO is to be completely removed, there is a tendency that the raw material batch price becomes high and the manufacturing cost increases. In the case of suppressing the increase in manufacturing cost, the lower limit of the MgO content is preferably 0.0001% or more, 0.0003% or more, 0.0005% or more, 0.001% or more, 0.003% or more, 0.005% or more, 0.007% or more, 0.009% or more, and particularly preferably 0.01% or more. In addition, MgO can also be actively contained according to the use of the glass of the present invention. For example, in the case of a colored appearance in a cooking top plate, etc., since the effect of the deterioration of the surface uneven state on the light transmittance can be allowed, the MgO content can be set to 0.5% or more, 1% or more, 2% or more, 3% or more, 4% or more, 5% or more, and particularly 5.5% or more.

[0058] B2O3 is a component that affects the ease of glass phase separation. It is also known that the electric field strength of Mg ions is higher than that of other cations, and phase separation is easy to occur in glasses containing B2O3 and MgO. By properly adjusting their ratio, it is easy to show phase separation caused by binodal decomposition, and as a result, it is easy to obtain the required light transmittance. Thus, in the case where a colored appearance is required in the use of, for example, a cooking top plate, the color of the coloring component added to the glass is easily reflected in the appearance of the glass, so it is easy to adjust the color tone of the glass, and it is easy to obtain colored glass with higher aesthetics. Therefore, MgO / (MgO+B2O3) (the value obtained by dividing the MgO content by the total amount of MgO and B2O3) is preferably greater than 0 and less than 0.99, greater than 0 and less than 0.95, greater than 0 and less than 0.90, greater than 0 and less than 0.85, 0.01-0.8, 0.1-0.8, 0.25-0.8, and particularly preferably 0.3-0.8. The reason why desired light transmittance is easily obtained when phase separation due to binodal decomposition occurs will be described later.

[0059] CaO is a component that reduces the viscosity of glass and improves the meltability and formability of glass. In addition, it is also a component used to adjust the linear thermal expansion coefficient, refractive index, etc. of low thermal expansion glass. Moreover, it is a component that affects the phase separation of glass. The CaO content is preferably 0-30%, 0-25%, 0-20%, 0-15%, 0-10%, 0-9%, 0-8%, 0-7%, 0-6%, 0-5%, 0-4%, 0-3%, 0-2%, 0-1.5%, 0-1%, 0-0.5%, 0-0.25%, and particularly preferably 0-0.1%. When the CaO content is too much, the linear thermal expansion coefficient becomes too large, and it is difficult to obtain glass with excellent heat resistance and thermal shock resistance. In addition, the homogeneity of the glass melt is easily reduced. In addition, the chemical durability of the glass is reduced, and the glass surface is easily deteriorated. As a result, the state of the surface concave and convex becomes worse, and it is difficult to obtain the desired light transmittance. In addition, since CaO is easily mixed as an impurity, if CaO is to be completely removed, there is a tendency that the raw material batch price becomes high and the manufacturing cost increases. In the case of suppressing the increase in manufacturing cost, the lower limit of the CaO content is preferably 0.0001% or more, 0.0003% or more, 0.0005% or more, 0.001% or more, 0.003% or more, 0.005% or more, 0.007% or more, 0.009% or more, and particularly preferably 0.01% or more.

[0060] SrO is a component that reduces the viscosity of glass and improves the meltability and formability of glass. It is also a component used to adjust the linear thermal expansion coefficient and refractive index of low thermal expansion glass. It is also a component that affects the phase separation of glass. The SrO content is preferably 0-30%, 0-25%, 0-20%, 0-15%, 0-10%, 0-9%, 0-8%, 0-7%, 0-6%, 0-5%, 0-4%, 0-3%, 0-2%, 0-1.5%, 0-1%, 0-0.5%, 0-0.25%, and particularly preferably 0-0.1%. When the SrO content is too much, the linear thermal expansion coefficient becomes too large, and it is difficult to obtain glass with excellent heat resistance and thermal shock resistance. In addition, it is easy to reduce the homogeneity of the glass melt. In addition, the chemical durability of the glass is reduced, and the glass surface is easily deteriorated. As a result, the state of the surface concave and convex becomes worse, and it is difficult to obtain the desired light transmittance. In addition, since SrO is easily mixed as an impurity, if SrO is to be completely removed, there is a tendency that the raw material batch price becomes high and the manufacturing cost increases. In the case of suppressing the increase in manufacturing cost, the lower limit of the SrO content is preferably 0.0001% or more, 0.0003% or more, 0.0005% or more, 0.001% or more, 0.003% or more, 0.005% or more, 0.007% or more, 0.009% or more, and particularly preferably 0.01% or more.

[0061] BaO is a component that reduces the viscosity of glass and improves the meltability and formability of glass. In addition, it is also a component used to adjust the linear thermal expansion coefficient and refractive index of low thermal expansion glass. In addition, it is a component that affects the phase separation of glass. The BaO content is preferably 0-30%, 0-25%, 0-20%, 0-15%, 0-10%, 0-9%, 0-8%, 0-7%, 0-6%, 0-5%, 0-4%, 0-3%, 0-2%, 0-1.5%, 0-1%, 0-0.5%, 0-0.25%, and particularly preferably 0-0.1%. When the BaO content is too much, the linear thermal expansion coefficient becomes too large, and it is difficult to obtain glass with excellent heat resistance and thermal shock resistance. In addition, the meltability of the glass is easily reduced. In addition, the chemical durability of the glass is reduced, and the glass surface is easily deteriorated. As a result, the state of the surface concave and convex becomes worse, and it is difficult to obtain the desired light transmittance. In addition, since BaO is easily mixed as an impurity, if BaO is to be completely removed, there is a tendency that the raw material batch price becomes high and the manufacturing cost increases. In the case of suppressing the increase in manufacturing cost, the lower limit of the BaO content is preferably 0.0001% or more, 0.0003% or more, 0.0005% or more, 0.001% or more, 0.003% or more, 0.005% or more, 0.007% or more, 0.009% or more, and particularly preferably 0.01% or more.

[0062] ZrO2 is a component that increases the Young's modulus and rigidity modulus of glass. It is also a component used to adjust the linear thermal expansion coefficient and refractive index of low thermal expansion glass. It is also a component that affects the phase separation of glass. The ZrO2 content is preferably 0-10%, 0-9%, 0-8%, 0-7%, 0-6%, 0-5%, 0-4%, 0-3%, 0-2%, 0-1.5%, 0-1%, 0-0.5%, 0-0.25%, 0-0.1%, and particularly preferably 0-0.01%. When the ZrO2 content is too much, the linear thermal expansion coefficient becomes too large, and it is difficult to obtain glass with excellent heat resistance and thermal shock resistance. Moreover, not only does it reduce the homogeneity of the glass melt and make it difficult to melt, but it also increases the viscosity and makes it difficult to clarify. It is also easy to make the glass difficult to form and reduce productivity. In addition, since ZrO2 is easily mixed as an impurity, if ZrO2 is to be completely removed, there is a trend that the raw material batch price becomes high and the manufacturing cost increases. In the case of suppressing the increase in manufacturing cost, the lower limit of the ZnO content is preferably 0.0001% or more, 0.0003% or more, 0.0005% or more, 0.001% or more, 0.003% or more, 0.005% or more, 0.007% or more, 0.009% or more, and particularly preferably 0.01% or more.

[0063] TiO2 is a component that reduces the viscosity of glass and improves the meltability and formability of glass by containing it in an appropriate amount. In addition, it is also a coloring component of glass that absorbs light of various wavelengths. It is known that in particular, when titanium and iron coexist, a coloring similar to ilmenite (FeTiO3) is exhibited. In addition, it is known that when titanium and tin coexist, the yellow color is enhanced. Moreover, TiO2 is a component that particularly affects the ease of phase separation. The TiO2 content is preferably 0-20%, 0-19%, 0-18%, 0-17%, 0-16%, 0-15%, 0-14%, 0-13%, 0-12%, 0-11%, 0-10%, 0-9%, 0-8%, 0-7%, 0-6%, 0-5%, 0-1%, 0-0.5%, and particularly preferably 0-0.1%. When the TiO2 content is too much, the meltability of the glass is easily reduced. Moreover, the glass is easily colored, and it is difficult to obtain the desired light transmittance. However, TiO2 is easily mixed in as an impurity. Therefore, if TiO2 is to be completely removed, there is a tendency that the raw material batch price becomes high and the manufacturing cost increases. In the case of suppressing the increase in manufacturing cost, the lower limit of the TiO2 content is preferably 0.0003% or more, 0.0005% or more, 0.001% or more, 0.005% or more, 0.01% or more, and particularly preferably 0.02% or more. In addition, the TiO2 content can also be controlled according to the use of the glass of the present invention to adjust the light transmittance. For example, in the case where a colored appearance is required in a cooking top plate, the TiO2 content can be set to 0.01% or more, 0.05% or more, 0.08% or more, 0.1% or more, 0.2% or more, and particularly 0.3% or more.

[0064] P2O5 is a component used to reduce the linear thermal expansion coefficient of low thermal expansion glass and adjust the refractive index. Moreover, it is a component that particularly affects the phase separation of glass. The P2O5 content is preferably 0-20%, more than 0% and less than 20%, 0.1-20%, 0.5-20%, 1-19%, 2-18%, 3-17%, 4-16%, 5-15%, 6-14%, and particularly preferably 7-14%. When the P2O5 content is too much, the linear thermal expansion coefficient becomes too large, and it is difficult to obtain glass with excellent heat resistance and thermal shock resistance. In addition, the homogeneity of the glass melt is easily reduced. In addition, the chemical durability of the glass is reduced, and the glass surface is easily deteriorated. As a result, the state of the surface concave and convex becomes worse, and it is difficult to obtain the desired light transmittance. In addition, P2O5 is easily mixed as an impurity. Therefore, if you want to completely remove P2O5, there is a tendency that the raw material batch price becomes higher and the manufacturing cost increases. In the case of suppressing the increase in manufacturing cost, the lower limit of the P2O5 content is preferably 0.0001% or more, 0.0003% or more, 0.0005% or more, 0.001% or more, 0.003% or more, 0.005% or more, 0.007% or more, 0.009% or more, and particularly preferably 0.01% or more.

[0065] ZnO, B2O3 and P2O5 are components that reduce the viscosity of glass and improve the solubility and formability of glass, and are also components that affect the phase separation of glass. Therefore, in order to improve the solubility and formability of glass, and to show the phase separation caused by binodal decomposition, and to achieve the desired light transmittance, ZnO+B2O3+P2O5 (the total amount of ZnO, B2O3 and P2O5) is preferably more than 0%, more than 0.1%, more than 0.5%, more than 1%, more than 2%, more than 3%, more than 4%, more than 5%, more than 6%, more than 7%, more than 8%, and particularly preferably more than 9%. On the other hand, when there is too much ZnO+B2O3+P2O5, the chemical durability of the glass is reduced, the surface of the glass is easily deteriorated, thereby worsening the state of the surface concave and convex, and it is difficult to obtain the desired light transmittance. Therefore, ZnO+B2O3+P2O5 is preferably less than 55%, less than 50%, less than 40%, less than 30%, less than 20%, less than 19%, less than 18%, less than 17%, less than 16%, less than 15%, less than 14%, less than 13%, less than 12%, and particularly preferably less than 11%.

[0066] Zn cation, B cation, P cation, O anion sometimes coordinate in the form of mutually compensating charge in glass and crystallized glass. In the case of forming electrically neutral coordination and forming a high chemical bond of covalent bonding, it is particularly easy to achieve chemical stability. The chemical resistance and thermal shock resistance of the glass with chemically stable coordination structure improve. In addition, ZnO, B2O3, P2O5 are respectively the components that reduce the viscosity of glass and improve the fusibility and formability of glass. Therefore, by properly controlling their ratio, it is possible to improve the chemical resistance and thermal shock resistance of glass, and to increase productivity. Therefore, in terms of mass ratio, (ZnO+B2O3+P2O5) / ZnO (the value obtained by dividing the total amount of ZnO, B2O3, and P2O5 by the ZnO content) is preferably greater than 1.001, greater than 1.05, greater than 1.1, greater than 1.2, greater than 1.3, greater than 1.5, greater than 2, greater than 5, and particularly preferably greater than 10, preferably less than 2000, less than 1600, less than 1000, less than 600, and particularly preferably less than 100.

[0067] Y2O3 is a component that reduces the viscosity of glass and improves the meltability and formability of glass. In addition, it is also a component used to increase the Young's modulus of low thermal expansion glass and adjust the linear thermal expansion coefficient and refractive index. It is also a component that affects the phase separation of glass. The Y2O3 content is preferably 0-10%, 0-9%, 0-8%, 0-7%, 0-6%, 0-5%, 0-4.5%, 0-4%, 0-3.5%, 0-3%, 0-2.5%, 0-2%, and particularly preferably 0-1.5%. When the Y2O3 content is too much, the linear thermal expansion coefficient becomes too large, and it is difficult to obtain glass with excellent heat resistance and thermal shock resistance. In addition, the homogeneity of the glass melt is easily reduced. In addition, the chemical durability of the glass is reduced, and the glass surface is easily deteriorated. As a result, the state of the surface concave and convex becomes worse, and it is difficult to obtain the desired light transmittance. In addition, Y2O3 is easily mixed as an impurity. Therefore, if Y2O3 is to be completely removed, there is a tendency that the raw material batch price becomes high and the manufacturing cost increases. In the case of suppressing the increase in manufacturing cost, the lower limit of the P2O5 content is preferably 0.0001% or more, 0.0003% or more, 0.0005% or more, 0.001% or more, 0.003% or more, 0.005% or more, 0.007% or more, 0.009% or more, and particularly preferably 0.01% or more.

[0068] As2O3 and Sb2O3 are highly toxic and may pollute the environment during the glass manufacturing process or the treatment of waste glass. Therefore, Sb2O3+As2O3 (the total amount of Sb2O3 and As2O3) is preferably less than 2%, less than 1%, less than 0.7%, less than 0.7%, less than 0.65%, less than 0.6%, less than 0.55%, less than 0.5%, less than 0.45%, less than 0.4%, less than 0.35%, less than 0.3%, less than 0.25%, less than 0.2%, less than 0.15%, less than 0.1%, less than 0.05%, less than 0.04%, less than 0.03%, less than 0.02%, less than 0.01%, less than 0.005%, less than 0.003%, less than 0.002%, less than 0.001%, less than 0.0005%, less than 0.0003%, less than 0.0001%, and it is particularly preferably substantially free of (specifically less than 0.0001%).

[0069] NiO is a component that reduces the viscosity of glass and improves the solubility and formability of glass by containing an appropriate amount. It is also a coloring component of glass that absorbs light of various wavelengths. Moreover, it is a component that affects the phase separation of glass. The NiO content is preferably 0-20%, 0-15%, 0-10%, 0-8%, 0-6%, 0-4%, 0-2%, 0-1%, 0-0.5%, 0-0.25%, 0-0.1%, 0-0.01%, and particularly preferably 0-0.005%. When the NiO content is too much, the solubility of the glass is easily reduced. In addition, the glass is easily colored and it is difficult to obtain the desired light transmittance. However, NiO is easily mixed from SUS parts in the manufacturing process, so if you want to completely remove NiO, there is a tendency that the raw material batch price becomes higher and the manufacturing cost increases. In the case of suppressing the increase of manufacturing cost, the lower limit of NiO content is preferably more than 0, 0.0001% or more, 0.0002% or more, and particularly preferably 0.0003% or more. In addition, the NiO content can be controlled to adjust the light transmittance according to the use of the glass of the present invention. For example, when a colored appearance is required in a cooking top plate, the NiO content can be set to 0.01% or more, 0.05% or more, 0.08% or more, 0.1% or more, 0.2% or more, and particularly 0.3% or more.

[0070] MnO2 is a component that reduces the viscosity of glass and improves the solubility and formability of glass by containing it in an appropriate amount. In addition, it is also a coloring component of glass that absorbs light of various wavelengths. Moreover, it is a component that affects the phase separation of glass. The MnO2 content is preferably 0-20%, 0-15%, 0-10%, 0-8%, 0-6%, 0-4%, 0-2%, 0-1%, 0-0.5%, 0-0.25%, 0-0.1%, 0-0.01%, and particularly preferably 0-0.005%. When the MnO2 content is too much, the solubility of the glass is easily reduced. In addition, the glass is easily colored and it is difficult to obtain the desired light transmittance. However, MnO2 is easily mixed in as an impurity, so if you want to completely remove MnO2, there is a tendency that the raw material batch price becomes higher and the manufacturing cost increases. In the case of suppressing the increase of manufacturing cost, the lower limit of MnO2 content is preferably more than 0, 0.0001% or more, 0.0002% or more, and particularly preferably 0.0003% or more. In addition, the MnO2 content can also be controlled to adjust the light transmittance according to the use of the glass of the present invention. For example, in the case where a colored appearance is required in a cooking top plate, the MnO2 content can also be set to 0.01% or more, 0.05% or more, 0.08% or more, 0.1% or more, 0.2% or more, and particularly 0.3% or more.

[0071] V2O5 is a component that reduces the viscosity of glass and improves the meltability and formability of glass by containing an appropriate amount. It is also a coloring component of glass that absorbs light of various wavelengths. Moreover, it is a component that affects the phase separation of glass. The V2O5 content is preferably 0-20%, 0-15%, 0-10%, 0-8%, 0-6%, 0-4%, 0-2%, 0-1%, 0-0.5%, 0-0.25%, 0-0.1%, 0-0.01%, and particularly preferably 0-0.005%. When the V2O5 content is too much, the meltability of the glass is easily reduced. In addition, the glass is easily colored and it is difficult to obtain the desired light transmittance. However, V2O5 is easily mixed in as an impurity. Therefore, if you want to completely remove V2O5, there is a tendency that the raw material batch price becomes higher and the manufacturing cost increases. In the case of suppressing the increase in manufacturing cost, the lower limit of the V2O5 content is preferably more than 0, 0.0001% or more, 0.0002% or more, and particularly preferably 0.0003% or more. In addition, the V2O5 content can be controlled to adjust the light transmittance according to the use of the glass of the present invention. For example, when a colored appearance is required in a cooking top plate, the V2O5 content can also be set to 0.01% or more, 0.05% or more, 0.1% or more, 0.2% or more, 0.25% or more, 0.3% or more, 0.4% or more, 0.5% or more, 0.6% or more, 0.7% or more, and particularly 0.75% or more.

[0072] Cr2O3 and V2O5 are components that reduce the viscosity of glass and improve the solubility and formability of glass by containing them in appropriate amounts. In addition, they are also coloring components of glass that absorb light of various wavelengths. In the case of glass that requires a black appearance for uses such as cooking tops, it is possible to consider containing a variety of coloring components, and Cr2O3 and V2O5 are components that are particularly easy to contribute to the blackening of glass, which can further improve the blackness of the glass. Therefore, in order to improve the blackness of the glass, Cr2O3+V2O5 (the combined amount of Cr2O3 and V2O5) is preferably 0.05% or more, 0.1% or more, 0.2% or more, 0.3% or more, 0.4% or more, 0.5% or more, 0.6% or more, 0.7% or more, 0.8% or more, and particularly preferably 0.9% or more. However, when the Cr2O3+V2O5 content is too high, the solubility of the glass is easily reduced. Therefore, the Cr2O3+V2O5 content is preferably less than 20%, less than 10%, less than 5%, less than 3%, less than 2%, and particularly preferably less than 1%.

[0073] CoO is a component that reduces the viscosity of glass and improves the meltability and formability of glass by containing an appropriate amount. In addition, it is also a coloring component of glass that absorbs light of various wavelengths. Moreover, it is also a component that affects the phase separation of glass. The CoO content is preferably 0-20%, 0-15%, 0-10%, 0-8%, 0-6%, 0-4%, 0-2%, 0-1%, 0-0.5%, 0-0.25%, 0-0.1%, 0-0.01%, and particularly preferably 0-0.005%. When the CoO content is too much, the meltability of the glass is easily reduced. In addition, the glass is easily colored and it is difficult to obtain the desired light transmittance. However, CoO is easily mixed as an impurity, so if you want to completely remove CoO, there is a tendency that the raw material batch price becomes higher and the manufacturing cost increases. In the case of suppressing the increase in manufacturing costs, the lower limit of the CoO content is preferably more than 0, 0.0001% or more, 0.0002% or more, and particularly preferably 0.0003% or more. In addition, the CoO content can be controlled to adjust the light transmittance according to the application of the glass of the present invention. For example, when a colored appearance is required in a cooking top plate, the CoO content can be set to 0.01% or more, 0.05% or more, 0.08% or more, 0.1% or more, 0.2% or more, and especially 0.3% or more.

[0074] CuO is a component that reduces the viscosity of glass and improves the meltability and formability of glass by containing an appropriate amount. In addition, it is also a coloring component of glass that absorbs light of various wavelengths. Moreover, it is a component that affects the phase separation of glass. The CuO content is preferably 0-20%, 0-15%, 0-10%, 0-8%, 0-6%, 0-4%, 0-2%, 0-1%, 0-0.5%, 0-0.25%, 0-0.1%, 0-0.01%, and particularly preferably 0-0.005%. When the CuO content is too much, the meltability of the glass is easily reduced. In addition, the glass is easily colored and it is difficult to obtain the desired light transmittance. However, CuO is easily mixed as an impurity, so if you want to completely remove CuO, there is a tendency that the raw material batch price becomes higher and the manufacturing cost increases. In the case of suppressing the increase in manufacturing cost, the lower limit of the CuO content is preferably more than 0, 0.0001% or more, 0.0002% or more, and particularly preferably 0.0003% or more. In addition, the CuO content can be controlled to adjust the light transmittance according to the application of the glass of the present invention. For example, when a colored appearance is required in a cooking top plate, the CuO content can be set to 0.01% or more, 0.05% or more, 0.08% or more, 0.1% or more, 0.2% or more, and especially 0.3% or more.

[0075] Nd2O3 is a component that reduces the viscosity of glass and improves the meltability and formability of glass by containing it in an appropriate amount. It is also a coloring component of glass that absorbs light of various wavelengths. Moreover, it is a component that affects the phase separation of glass. The Nd2O3 content is preferably 0-20%, 0-15%, 0-10%, 0-8%, 0-6%, 0-4%, 0-2%, 0-1%, 0-0.5%, 0-0.25%, 0-0.1%, 0-0.01%, and particularly preferably 0-0.005%. When the Nd2O3 content is too much, the glass is easily colored and it is difficult to obtain the desired light transmittance. In addition, the Nd2O3 content can also be controlled according to the use of the glass of the present invention to adjust the light transmittance. For example, when a colored appearance is required in a cooking top plate, the Nd2O3 content can also be set to 0.01% or more, 0.05% or more, 0.08% or more, 0.1% or more, 0.2% or more, and particularly 0.3% or more.

[0076] WO3 is a component that reduces the viscosity of glass and improves the meltability and formability of glass by containing an appropriate amount. It is also a coloring component of glass that absorbs light of various wavelengths. It is also a component that affects the phase separation of glass. The WO3 content is preferably 0-20%, 0-15%, 0-10%, 0-8%, 0-6%, 0-4%, 0-2%, 0-1%, 0-0.5%, 0-0.25%, 0-0.1%, 0-0.01%, and particularly preferably 0-0.005%. When the WO3 content is too much, the glass is easily colored and it is difficult to obtain the desired light transmittance. In addition, the WO3 content can also be controlled according to the use of the glass of the present invention to adjust the light transmittance. For example, when a colored appearance is required in a cooking top plate, the WO3 content can also be set to 0.01% or more, 0.05% or more, 0.08% or more, 0.1% or more, 0.2% or more, and particularly 0.3% or more.

[0077] Fe2O3, TiO2, NiO, MoO3, Cr2O3, MnO2, V2O5, CoO, CuO, Nd2O3, and WO3 are components that reduce the viscosity of glass and improve the solubility and formability of glass by containing them in appropriate amounts. In addition, they are also coloring components of glass that absorb light of various wavelengths. According to the use of the glass of the present invention, it is necessary to control the total amount of Fe2O3, TiO2, NiO, MoO3, Cr2O3, MnO2, V2O5, CoO, CuO, Nd2O3, and WO3 (Fe2O3+TiO2+NiO+MoO3+Cr2O3+MnO2+V2O5+CoO+CuO+Nd2O3+WO3) to adjust the light transmittance. In particular, when a colored appearance is required in a cooking top plate, etc., Fe2O3+TiO2+NiO+MoO3+Cr2O3+MnO2+V2O5+CoO+CuO+Nd2O3+WO3 is preferably greater than 0, 0.0001%, 0.0002%, 0.0003%, 0.05%, 0.1%, 0.2%, 0.3%, 0.5%, 0.7%, and particularly preferably greater than 0.9%. However, when the content of Fe2O3+TiO2+NiO+MoO3+Cr2O3+MnO2+V2O5+CoO+CuO+Nd2O3+WO3 is too high, the solubility of the glass will easily decrease. Therefore, the content of Fe2O3+TiO2+NiO+MoO3+Cr2O3+MnO2+V2O5+CoO+CuO+Nd2O3+WO3 is preferably less than 20%, less than 10%, less than 5%, less than 3%, less than 2%, and particularly preferably less than 1%.

[0078] SiO2 and Al2O3 are components that form the glass skeleton. On the other hand, Fe2O3, TiO2, NiO, MoO3, Cr2O3, MnO2, V2O5, CoO, CuO, Nd2O3, and WO3 are components that reduce the viscosity of the glass and improve the meltability and formability of the glass. In addition, they are also coloring components of the glass that absorb light of various wavelengths. According to the use of the glass of the present invention, it is necessary to control the total amount of Fe2O3, TiO2, NiO, MoO3, Cr2O3, MnO2, V2O5, CoO, CuO, Nd2O3, and WO3 to adjust the light transmittance, but at the same time, it is necessary to control the viscosity of the molten glass and form it into a desired shape. In particular, when a colored appearance is required in a cooking top plate or the like, in order to achieve a viscosity that allows easy light transmission and molding by various molding methods, it is preferred to appropriately control the total amount of SiO2 and Al2O3 (SiO2 + Al2O3) and the total amount of Fe2O3, TiO2, NiO, MoO3, Cr2O3, MnO2, V2O5, CoO, CuO, Nd2O3, and WO3 (Fe2O3 + TiO2 + NiO + MoO3, Cr2O3 + MnO2 + V2O5 + CoO + The ratio of (SiO2+Al2O3) / (Fe2O3+TiO2+NiO+MoO3, Cr2O3+MnO2+V2O5+CoO+CuO+Nd2O3+WO3) is preferably greater than 0, more than 5, more than 10, more than 15, more than 20, more than 25, more than 30, more than 35, more than 40, and particularly preferably more than 45, preferably less than 10000, less than 5000, and particularly preferably less than 3000.

[0079] As long as the glass of the present invention can obtain the chemical durability of the glass and the required light transmittance, heat resistance and heat shock resistance, etc., in addition to the above-mentioned components, it can also contain SO3, Cl2, La2O3, Ta2O5, Nb2O5, RfO2, etc. in a total amount of less than 10%. However, the raw material batch price of the above-mentioned components is high, and there is a trend of increasing manufacturing costs. Therefore, unless there are special circumstances, it is not necessary to add them. The total amount of these components is preferably less than 5%, less than 4%, less than 3%, less than 2%, less than 1%, less than 0.5%, less than 0.4%, less than 0.3%, less than 0.2%, less than 0.1%, less than 0.05%, less than 0.05%, less than 0.049%, less than 0.048%, less than 0.047%, less than 0.046%, and particularly preferably less than 0.045%.

[0080] The glass of the present invention may contain trace components such as H2, CO2, CO, H2O, He, Ne, Ar, N2, etc., each within 0.1%, in addition to the above-mentioned components, as long as the chemical durability of the glass and the required light transmittance, heat resistance, and heat shock resistance can be achieved. In addition, when Ag, Au, Pd, Ir, Sc, Ce, Pr, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, Lu, Ac, Th, Pa, U, etc. are intentionally added, the cost of raw materials increases, and as a result, there is a tendency for the manufacturing cost to increase. However, when the glass containing Ag or Au, etc. is subjected to light irradiation or heat treatment, an aggregate of these components can be formed, and crystallization can be intentionally promoted with this as a starting point. Moreover, Pd, etc. have various catalytic effects, and by containing these components, special properties can be given to the glass. In view of this situation, when the purpose is to promote crystallization or impart other functions, the above-mentioned components can be contained in an amount of less than 1%, less than 0.5%, less than 0.3%, or less than 0.1%, respectively. When these purposes are not particularly required, it is preferably less than 500 ppm, less than 300 ppm, or less than 100 ppm, and particularly preferably less than 10 ppm.

[0081] In addition, the glass of the present invention can also be a crystallized glass. The content range of each component at this time is the same as the above-mentioned range. As the seed crystal in the crystallized glass, ZnAl2O4 (zinc spinel), Al2SiO5, ZrO2, etc. can be enumerated.

[0082] The glass of the present invention preferably contains, by mass%, 40 to 90% of SiO2, 5 to 35% of Al2O3, more than 0% and less than 35% of ZnO, 0 to 5% of Li2O+Na2O+K2O, and more than 0% of Fe2O3.

[0083] More preferably, it contains, by mass%, 40 to 90% SiO2, 5 to 35% Al2O3, more than 0% and less than 35% ZnO, 0% to 5% Li2O+Na2O+K2O, more than 0% Fe2O3, and 0 to 5% HfO2.

[0084] It is more preferred that it contains, in mass%, 40 to 90% SiO2, 5 to 35% Al2O3, more than 0% and less than 35% ZnO, 0% to 5% Li2O+Na2O+K2O, more than 0% Fe2O3, 0 to 5% HfO2, less than 5 ppm Pt, less than 5 ppm Rh, and Al2O3 / ZnO is 0.14 to 2, and ZnO / (SiO2+B2O3) is 0.05 to 0.7.

[0085] It is further preferred that it contains, in mass%, 45-85% SiO2, 5-35% Al2O3, 6-35% ZnO, 0.001-3% Li2O+Na2O+K2O, more than 0.002% Fe2O3, 0-0.5% HfO2, less than 5 ppm Pt, less than 5 ppm Rh, and Al2O3 / ZnO is 0.14-2, and ZnO / (SiO2+B2O3) is 0.05-0.7.

[0086] It is further preferred that it contains, in mass%, 45-85% SiO2, 5-35% Al2O3, 12-35% ZnO, 0.001-1% Li2O+Na2O+K2O, more than 0.002% Fe2O3, 0-0.5% HfO2, less than 5 ppm Pt, less than 5 ppm Rh, and Al2O3 / ZnO is 0.14-2, and ZnO / (SiO2+B2O3) is 0.05-0.7.

[0087] It is further preferred that it contains, in mass%, 45-85% SiO2, 5-35% Al2O3, 18-35% ZnO, 0.001-0.5% Li2O+Na2O+K2O, more than 0.002% Fe2O3, 0-0.5% HfO2, less than 5 ppm Pt, less than 5 ppm Rh, and Al2O3 / ZnO is 0.14-2, and ZnO / (SiO2+B2O3) is 0.05-0.7.

[0088] It is further preferred that it contains, in mass%, 45-85% SiO2, 5-35% Al2O3, 18-35% ZnO, 0.001-0.39% Li2O+Na2O+K2O, more than 0.002% Fe2O3, 0-0.5% HfO2, less than 5 ppm Pt, less than 5 ppm Rh, and Al2O3 / ZnO is 0.14-2, and ZnO / (SiO2+B2O3) is 0.05-0.7.

[0089] It is further preferred that it contains, in mass%, 45-85% SiO2, 5-35% Al2O3, 18-35% ZnO, 0.001-0.39% Li2O+Na2O+K2O, more than 0.002% Fe2O3, 0-0.5% HfO2, less than 5 ppm Pt, less than 5 ppm Rh, more than 0% MoO3, more than 0% SnO2, more than 0% Cr2O3, and Al2O3 / ZnO is 0.14-2, and ZnO / (SiO2+B2O3) is 0.05-0.7.

[0090] It is further preferred that it contains, in mass%, 45-85% SiO2, 5-35% Al2O3, 18-35% ZnO, 0.001-0.39% Li2O+Na2O+K2O, more than 0.002% Fe2O3, 0-0.5% HfO2, less than 5 ppm Pt, less than 5 ppm Rh, more than 0.0001% MoO3, more than 0.01% SnO2, and more than 0% Cr2O3, and Al2O3 / ZnO is 0.14-2, and ZnO / (SiO2+B2O3) is 0.05-0.7.

[0091] It is further preferred that the composition contains, by mass%, 45 to 85% SiO2, 5 to 35% Al2O3, 18 to 35% ZnO, 0.001 to 0.39% Li2O+Na2O+K2O, 0.002% or more Fe2O3, 0 to 0.5% HfO2, 5 ppm or less Pt, 5 ppm or less Rh, 0.0001% or more MoO3, 0.1% or more SnO2, 0.0001% or more Cr2O3, and Al2O3 / ZnO is 0.14 to 2, and ZnO is 0.001 to 0.002. O / (SiO2+B2O3) is 0.05~0.7, (ZnO+B2O3+P2O5) / ZnO is above 1.001, Fe2O3+TiO2+NiO+MoO3, Cr2O3+MnO2+V2O5+CoO+CuO+Nd2O3+WO3 exceed 0%, (SiO2+Al2O3) / (Fe2O3+TiO2+NiO+MoO3+Cr2O3+MnO2+V2O5+CoO+CuO+Nd2O3+WO3) is above 10.

[0092] The glass of the present invention having the above-mentioned composition can easily achieve low thermal expansion, as well as desired light transmittance, heat resistance, and thermal shock resistance.

[0093] Furthermore, when the glass of the present invention is a crystallized glass, by having the above-mentioned composition, low thermal expansion, and desired light transmittance, heat resistance, and thermal shock resistance can be easily achieved.

[0094] The β-OH value of the glass of the present invention is preferably greater than 0 / mm and less than 2 / mm, 0.001 to 2 / mm, 0.01 to 1.5 / mm, 0.02 to 1.5 / mm, 0.03 to 1.2 / mm, 0.04 to 1.5 / mm, 0.05 to 1.4 / mm, 0.06 to 1.3 / mm, 0.07 to 1.2 / mm, 0.08 to 1.1 / mm, 0.08 to 1 / mm, 0.08 to 0.9 / mm, 0.08 to 0.85 / mm, 0.08 to 0.8 / mm, 0.08 to 0.75 / mm, 0.08 to 0.74 / mm, 0.08 to 0.73 / mm, 0.08 to 0.72 / mm, 0.08 to 0.71 / mm, and particularly preferably 0.08 to 0.7 / mm. When the β-OH value is within the above range, the quality of the glass is not easy to reduce. That is, when the β-OH value is too small, the amount of water vapor produced when the glass batch material is melted is reduced. Therefore, the stirring effect on the glass batch material brought by the generation of water vapor is weakened, it is difficult to promote the initial reaction of the glass batch material, and the manufacturing load is easy to increase. On the other hand, when the β-OH value is too large, it is easy to produce bubbles at the interface of the metal parts or refractory parts of Pt and the glass melt, which is easy to reduce the quality of the glass product. In addition, there is a possibility that the glass transition temperature, yield point, strain point, annealing point, softening point are reduced, or the linear thermal expansion coefficient is improved and the heat resistance and heat shock resistance are deteriorated, so it becomes unsuitable for use at high temperatures. In addition, the β-OH value changes with the changes of the raw materials, melting atmosphere, melting temperature, melting time, etc. used, and therefore, these conditions can be changed as needed to adjust the β-OH value. For example, the β-OH value can be increased by increasing the amount of hydroxide in the raw material, or melting by heating with a burner, or increasing the melting temperature. Furthermore, the β-OH value can be increased by extending the melting time in a sealed state and shortening the melting time in an unsealed state.

[0095] The linear thermal expansion coefficient of the glass of the present invention at 30-380°C is preferably 60×10 ﹣7 / ℃ below, 56×10 ﹣7 / ℃ or less, 52×10 ﹣7 / ℃ below, 48×10 ﹣7 / ℃ below, 44×10 ﹣7 / ℃ below, 40×10 ﹣7 / ℃ below, 36×10 ﹣7 / ℃ below, 34×10 ﹣7 / ℃ or less, 32×10 ﹣7 / ℃ or less, 29.5×10 ﹣7 / ℃ or less, 27.5×10 ﹣7 / ℃ or less, 25.5×10 ﹣7 / ℃ or less, 23.5×10 ﹣7 / ℃ or less, 21.5×10 ﹣7 / ℃ or less, 19.5×10 ﹣7 / ℃ below, 18×10 ﹣7 / ℃ below, 17.5×10 ﹣7 / ℃ below, 17×10 ﹣7 / ℃ below, 16.5×10 ﹣7 / ℃ below, 15.5×10 ﹣7 / ℃ below, 15×10 ﹣7 / ℃ below, 14.5×10 ﹣7 / ℃ below, 14×10 ﹣7 / °C or less, particularly preferably 13.5×10 ﹣7 / ℃ below.

[0096] In addition, the linear thermal expansion coefficient of the glass of the present invention at 30 to 750°C is preferably 60×10 ﹣7 / ℃ below, 56×10 ﹣7 / ℃ or less, 52×10 ﹣7 / ℃ below, 48×10 ﹣7 / ℃ below, 44×10 ﹣7 / ℃ below, 40×10 ﹣7 / ℃ below, 36×10 ﹣7 / ℃ below, 34×10 ﹣7 / ℃ or less, 32×10 ﹣7 / ℃ or less, 29.5×10 ﹣7 / ℃ or less, 27.5×10 ﹣7 / ℃ or less, 25.5×10 ﹣7 / ℃ or less, 23.5×10 ﹣7 / ℃ or less, 21.5×10 ﹣7 / ℃ or less, 19.5×10 ﹣7 / ℃ below, 18×10 ﹣7 / ℃ below, 17.5×10 ﹣7 / ℃ below, 17×10 ﹣7 / ℃ below, 16.5×10 ﹣7 / ℃ below, 15.5×10 ﹣7 / ℃ below, 15×10 ﹣7 / ℃ below, 14.5×10 ﹣7 / ℃ below, 14×10 ﹣7 / °C or less, particularly preferably 13.5×10 ﹣7 / ℃ or less. When the linear thermal expansion coefficient is too large, the heat resistance and thermal shock resistance are low, and it is difficult to use at high temperatures. In addition, it is difficult to apply it to applications that require positional stability. In particular, when it is envisioned to be used as a cooking top plate, in order to avoid damage caused by heat or strain, the linear thermal expansion coefficient is preferably lower. Although there is no particular lower limit for the linear thermal expansion coefficient, in reality, the linear thermal expansion coefficient at a temperature of 30 to 380℃ is -70×10 ﹣7 / ℃, the linear thermal expansion coefficient at 30~750℃ is -60×10 ﹣7 / ℃.

[0097] The light transmittance of the glass of the present invention should be appropriately controlled for each wavelength according to the application. Specifically, in the application requiring high light transmittance in the ultraviolet region, the light transmittance at a thickness of 4 mm and a wavelength of 300 nm is preferably 0.1% or more, 1% or more, 5% or more, 10% or more, 20% or more, 24% or more, 28% or more, 30% or more, 40% or more, 43% or more, 44% or more, and particularly preferably 45% or more. In particular, when used in UV curing of resins, fluorescence detection of printed materials, insect attractants, etc., it is preferred that the light transmittance at a wavelength of 300 nm is higher. On the other hand, in the application requiring low light transmittance in the ultraviolet region, the light transmittance at a thickness of 4 mm and a wavelength of 300 nm is preferably 50% or less, 40% or less, 30% or less, 20% or less, 10% or less, 5% or less, 4% or less, 3% or less, 2% or less, and particularly preferably 1% or less. In particular, when UV cutoff energy is required in chemical containers or filters, it is preferred that the light transmittance at a wavelength of 300 nm is lower. In addition, the preferred light transmittance varies depending on the application and is therefore not limited to the specific numerical range described above.

[0098] The glass of the present invention is preferably 0.1% or more, 1% or more, 5% or more, 10% or more, 20% or more, 30% or more, 36% or more, 40% or more, 50% or more, 60% or more, 70% or more, 80% or more, 82% or more, 83% or more, and particularly preferably 84% or more in applications requiring colorless transparency such as displays. In particular, it is preferred that the light transmittance at a wavelength of 380nm is higher. When the light transmittance at a wavelength of 380nm is too low, it will be colored yellow, and it is difficult to obtain the desired colorless transparency. On the other hand, in applications requiring low light transmittance in the near ultraviolet region, the light transmittance at a thickness of 4mm and a wavelength of 380nm is preferably 50% or less, 40% or less, 30% or less, 20% or less, 10% or less, 4% or less, 3% or less, 2% or less, and particularly preferably 1% or less. In particular, when used in chemical containers or ultraviolet-blue light shielding applications, or when a colored appearance is required in a cooker top plate, the light transmittance at a wavelength of 380 nm is preferably lower. In addition, the preferred light transmittance varies depending on the application, and therefore, is not limited to the specific numerical range described above.

[0099] In applications where high light transmittance in the visible light region is required, the glass of the present invention preferably has a light transmittance of 0.1% or more, 1% or more, 5% or more, 10% or more, 20% or more, 30% or more, 40% or more, 50% or more, 60% or more, 70% or more, 80% or more, 82% or more, 84% or more, 85% or more, 86% or more, 87% or more, and particularly preferably 88% or more in applications where high light transmittance in the visible light region is required, with a thickness of 4 mm and a wavelength of 555 nm. The light transmittance is preferably 50% or less, 40% or less, 30% or less, 20% or less, 10% or less, 8% or less, 6% or less, 4% or less, 3% or less, 2% or less, and particularly preferably 1% or less in applications where low light transmittance in the visible light region is required, with a thickness of 4 mm and a wavelength of 555 nm. In particular, when used in chemical containers or ultraviolet light to green light shielding applications, or when a colored appearance is required in a cooker top plate, it is preferred that the light transmittance at a wavelength of 555nm is lower. In addition, the preferred light transmittance varies depending on the application, and therefore, is not limited to the specific numerical range described above.

[0100] In the application where high light transmittance in the near-infrared region is required, the light transmittance of the glass of the present invention at a thickness of 4 mm and a wavelength of 800 nm is preferably 0.1% or more, 1% or more, 5% or more, 10% or more, 20% or more, 30% or more, 40% or more, 50% or more, 60% or more, 70% or more, 80% or more, 82% or more, 84% or more, 85% or more, 86% or more, 87% or more, and particularly preferably 88% or more. In particular, when used in medical applications such as vein authentication, it is preferred that the light transmittance at a wavelength of 800 nm is higher. On the other hand, in the application where low light transmittance in the near-infrared region is required, the light transmittance at a thickness of 4 mm and a wavelength of 800 nm is preferably 50% or less, 40% or less, 30% or less, 20% or less, 10% or less, 8% or less, 6% or less, 4% or less, 3% or less, 2% or less, and particularly preferably 1% or less. In particular, when used in chemical containers or visible light shielding applications, or when a colored appearance is required in a cooker top plate, it is preferred that the light transmittance at a wavelength of 800 nm is lower. In addition, the preferred light transmittance varies depending on the application, and therefore, is not limited to the specific numerical range described above.

[0101] In the application where high light transmittance in the infrared region is required, the light transmittance of the glass of the present invention at a thickness of 4 mm and a wavelength of 1200 nm is preferably 0.1% or more, 1% or more, 5% or more, 10% or more, 20% or more, 30% or more, 40% or more, 50% or more, 60% or more, 70% or more, 80% or more, 81% or more, 83% or more, 85% or more, 86% or more, 87% or more, and particularly preferably 88% or more. In particular, when used in infrared communication applications such as infrared cameras or remote controllers, it is preferred that the light transmittance at a wavelength of 1200 nm is higher. On the other hand, in the application where low light transmittance in the infrared region is required, the light transmittance at a thickness of 4 mm and a wavelength of 1200 nm is preferably 50% or less, 40% or less, 30% or less, 20% or less, 10% or less, 8% or less, 6% or less, 4% or less, 3% or less, 2% or less, and particularly preferably 1% or less. In particular, when used for infrared shielding purposes, it is preferred that the light transmittance at a wavelength of 1200 nm is lower. In addition, the preferred light transmittance varies depending on the application, and therefore is not limited to the specific numerical range described above.

[0102] The Young's modulus of the glass of the present invention is preferably 65 GPa or more, 67 GPa or more, 70 GPa or more, 72 GPa or more, 75 GPa or more, 78 GPa or more, and particularly preferably 80 GPa or more. Thus, even if a reflective film or the like is applied to the surface of the glass of the present invention, the glass is not easily warped, and as a result, the product of the present invention can achieve high functionality.

[0103] The rigidity modulus of the glass of the present invention is preferably 20 to 55 GPa, 25 to 50 GPa, 27 to 48 GPa, 29 to 46 GPa, and particularly preferably 30 to 45 GPa. Whether the rigidity modulus is too low or too high, the glass is easily broken.

[0104] The Poisson's ratio of the glass of the present invention is preferably 0.35 or less, 0.32 or less, 0.3 or less, 0.28 or less, or 0.26 or less, and particularly preferably 0.25 or less. When the Poisson's ratio is too large, the glass of the present invention is easily broken.

[0105] The density of the glass of the present invention is preferably 2.20 to 3.50 g / cm 3 2.30~3.40g / cm 3 2.40~3.35g / cm 3 2.50~3.30g / cm 3 , particularly preferably 2.55 to 3.25 g / cm 3 If the density is too low, the air permeability of the glass increases, and the glass may be contaminated during long-term storage. On the other hand, if the density is too high, the weight per unit area increases, making it difficult to handle.

[0106] Generally, when a phase separation of spinodal decomposition occurs (a phase separation mode in which the second phase and subsequent phases exist in the form of a continuous mixture of the first phase with the largest volume fraction), it is easy to have unevenness on the glass surface due to differences in the chemical durability of each phase. After in-depth research, the inventors of the present invention found that by annealing the glass of the present invention at a temperature above the glass transition temperature, it can be phase-separated into two or more different phases. In many cases, the phase separation state is binodal decomposition (a phase separation mode in which the second phase and subsequent phases are dispersed in the first phase with the largest volume fraction and are mixed in a spherical shape). It is also found that by appropriately controlling the glass composition, annealing conditions, etc., it is possible to arbitrarily present the phase separation caused by binodal decomposition, and finish the glass surface to easily obtain the desired light transmittance. According to the above situation, the glass of the present invention can be composed of only a single glass phase, or it can be a state containing two or more phases. In addition, for example, when a white or milky white appearance is required for use as a cooking top plate, the glass of the present invention is particularly preferably a state containing two or more phases. In this case, by appropriately controlling the annealing conditions, etc., it is possible to easily obtain glass with a white or milky appearance. In addition, the phase after the second phase can be any state of a glass state, a crystalline state, a gaseous state, or a liquid state. In addition, the phase after the second phase can be composed of metal oxides, metals, organic matter, etc., and there is no limitation on the composition. In addition, the shape of the phase after the second phase is preferably flaky, granular, spherical, circular, elliptical, linear, etc., and can be a single shape or a shape combining various shapes. In addition, the phase separation can be grasped by measuring the surface shape using SEM (scanning electron microscope) or AFM (atomic force microscope) after etching with liquids such as hydrofluoric acid. In addition, the chemical bonding state in the sample can also be confirmed by using FT-IR spectroscopy, Raman spectroscopy, etc., and the relevant information of the phase separation can be obtained in a non-destructive manner. The phase separation state recorded in this specification can be grasped by a method that can be easily remembered by a technician in the field.

[0107] Regarding the size of the phase after the second phase, it is preferably less than 100 μm, less than 50 μm, less than 30 μm, less than 10 μm, less than 5 μm, less than 4 μm, less than 3 μm, less than 2 μm, less than 1 μm, less than 0.5 μm, less than 0.3 μm, less than 0.2 μm, and particularly preferably less than 0.1 μm. When the longest part of the phase after the second phase is too long, the surface roughness of the glass becomes large, and it is difficult to obtain the desired light transmittance. In addition, the lower limit of the longest part of each phase after the second phase is not particularly limited, and in reality it is more than 0.01 nm.

[0108] In the case of the phase after the second phase being crystalline state, the crystallization crystal system is preferably any crystal system in hexagonal system, trigonal system, cubic system, tetragonal system, orthorhombic system, monoclinic system. Although it can also be triclinic system, in this case, birefringence easily occurs in crystallization, as a result, light scattering and is difficult to obtain required light transmittance. In the case of triclinic system, it is necessary to design the composition of the first phase in a lower mode with the refractive index difference of crystallization and the first phase.

[0109] When the glass of the present invention is in a state of containing two or more phases, if the refractive index difference between the second phase and the first phase is large, light is scattered at the boundary between the phases, and it is difficult to obtain the desired light transmittance. The refractive index difference between the phases is preferably 1.5 at each wavelength of nd (587.6nm), nC (656.3nm), nF (486.1nm), ne (546.1nm), ng (435.8nm), nh (404.7nm), ni (365.0nm), nF' (480.0nm), n785 (785nm), n1310 (1310nm), and n1550 (1550nm), which are representative wavelengths for refractive index measurement. The refractive index of each phase can be measured using a precision refractometer (KPR-2000 manufactured by Shimadzu Corporation) or the like.

[0110] The refractive index nd (587.6nm) of the glass of the present invention is preferably less than 2.50, less than 2.40, less than 2.20, less than 2.00, less than 1.80, less than 1.70, less than 1.60, less than 1.58, less than 1.55, less than 1.54, and more preferably less than 1.53. In addition, it is preferably more than 1.20, more than 1.25, more than 1.30, more than 1.35, more than 1.38, more than 1.40, more than 1.42, and more preferably more than 1.43. When the refractive index is too high, light may be scattered on the surface or end face and it is difficult to obtain the desired light transmittance. On the other hand, when the refractive index is too low, the refractive index difference between the glass of the present invention and air becomes small, it may be difficult to identify the glass of the present invention, and the processing in the manufacture becomes difficult.

[0111] The lightness L* of the glass of the present invention should be appropriately controlled according to the application. In applications requiring high lightness, the lightness L* at a thickness of 4 mm is preferably 5 or more, 10 or more, 20 or more, 30 or more, 40 or more, 50 or more, 60 or more, 70 or more, 80 or more, 85 or more, 90 or more, 94 or more, 95 or more, 96 or more, 96 or more, 96.1 or more, 96.3 or more, and particularly preferably 96.5 or more. When the lightness L* is too small, it is gray regardless of the size of the chromaticity, and there is a tendency for the appearance to look dark. Therefore, in applications requiring high brightness such as displays, it is preferred that the lightness L* is large. On the other hand, in applications requiring low lightness, the lightness L* at a thickness of 4 mm is preferably 45 or less, 40 or less, 35 or less, 30 or less, 25 or less, 20 or less, 15 or less, and particularly preferably 10 or less. In particular, in the case of use in chemical containers, visible light shielding applications, etc., or in the case where a black appearance is required in a cooker top plate, etc., it is preferred that the lightness L* is low. In addition, since the appropriate lightness L* varies depending on the application, it is not limited to the specific numerical range described above.

[0112] In applications where high colorless transparency is required, the chromaticity a* of the glass of the present invention is preferably within ±50, within ±40, within ±30, within ±20, within ±10, within ±5, within ±3, within ±1, within ±0.9, within ±0.8, within ±0.7, within ±0.6, and particularly preferably within ±0.5 when the thickness is 4 mm. When the lightness a* is too large in the negative direction, it tends to be green, and when it is too large in the positive direction, it tends to be red. On the other hand, when it is necessary to color it darker green or red, the chromaticity a* at a thickness of 4 mm is preferably ±6 or more, ±7 or more, ±8 or more, and particularly preferably ±9 or more. In addition, when it is colored black, the chromaticity a* at a thickness of 4 mm is preferably +10 or more, +12 or more, +14 or more, +16 or more, +17 or more, +18 or more, +19 or more, and particularly preferably +20 or more. In addition, since the appropriate chromaticity a* varies depending on the application, it is not limited to the specific numerical range described above.

[0113] In applications where high colorless transparency is required, the chromaticity b* of the glass of the present invention at a thickness of 4 mm is preferably within ±50, within ±45, within ±40, within ±30, within ±20, within ±10, within ±5, within ±3, within ±1, within ±0.9, within ±0.8, within ±0.7, within ±0.6, and particularly preferably within ±0.5. When the lightness b* is too large in the negative direction, it tends to be bluish, and when it is too large in the positive direction, it tends to be yellowish. On the other hand, when a darker blue or yellow color is required, the chromaticity b* at a thickness of 4 mm is preferably greater than ±6, greater than ±7, greater than ±8, and particularly preferably greater than ±9. In addition, when colored in black, the chromaticity b* at a thickness of 4 mm is preferably +10 or more, +12 or more, +16 or more, +20 or more, +24 or more, +28 or more, +32 or more, +36 or more, +40 or more, +42 or more, +44 or more, +46 or more, +48 or more, and particularly preferably +50 or more. In addition, the appropriate chromaticity b* varies depending on the application, and is therefore not limited to the specific numerical range described above.

[0114] In the glass of the present invention, the temperature at which the slope of the thermal expansion curve of the glass changes is treated as the glass transition temperature (glass transition point). The glass transition temperature of the glass of the present invention is preferably 710°C or more, 712°C or more, 714°C or more, 716°C or more, 718°C or more, 720°C or more, 722°C or more, 724°C or more, 726°C or more, 728°C or more, and particularly preferably 730°C or more. When the glass transition temperature is too low, the glass flows excessively and is difficult to be formed into a desired shape. In addition, when the glass transition temperature is too low, the glass is easily deformed when used at high temperatures.

[0115] In the glass of the present invention, the temperature at which the slope of the thermal expansion curve of the glass changes at a temperature above the glass transition temperature is treated as the yield point. The yield point of the glass of the present invention is preferably above 750°C, above 752°C, above 754°C, above 758°C, above 762°C, above 764°C, above 766°C, above 768°C, and particularly preferably above 770°C. When the yield point is too low, the glass flows excessively and is difficult to be formed into a desired shape. In addition, when the yield point is too low, the glass is easily deformed when used at high temperatures.

[0116] The liquidus temperature of the glass of the present invention is preferably 1600° C. or less, 1580° C. or less, 1560° C. or less, 1540° C. or less, 1520° C. or less, 1500° C. or less, 1480° C. or less, 1460° C. or less, 1440° C. or less, 1420° C. or less, 1410° C. or less, 1400° C. or less, 1380° C. or less, 1360° C. or less, 1340° C. or less, 1320° C. or less, 1300° C. or less, 1290° C. or less, 1280° C. or less, 1270° C. or less, 1260° C. or less, 1250° C. or less, 1240° C. or less, 1230° C. or less, 1200° C. or less, or 1190° C. or less, and particularly preferably 1180° C. or less. When the liquidus temperature is too high, devitrification is likely to occur during production. On the other hand, if the temperature is below 1480°C, it is easy to manufacture by a roll pressing method, etc., if the temperature is below 1410°C, it is easy to manufacture by an overflow method, etc., if the temperature is below 1350°C, it is easy to manufacture by a bushing method, etc., and if the temperature is below 1300°C, it is easy to manufacture by a Danner method, etc. The liquidus viscosity of the glass of the present invention is preferably 10 2.7 dPa·s or more, 10 2.8 dPa·s or more, 10 3.0 dPa·s or more, 10 3.2 dPa·s or more, 10 3.4 dPa·s or more, 10 3.6 dPa·s or more, 10 3.8 dPa·s or more, 10 4.0 dPa·s or more, 10 4.2 dPa·s or more, 10 4.4 dPa·s or more, 10 4.6 dPa·s or more, 10 4.8 dPa·s or more, 10 5.0 dPa·s or more, 10 5.2 dPa·s or more, 10 5.4 dPa·s or more, 10 5.6 dPa·s or more, 10 5.8 dPa·s or more, 10 5.9 dPa·s or more, particularly preferably 10 6.0 By setting it in this way, the glass will not easily lose clarity during molding.

[0117] The glass of the present invention preferably has high water resistance as a representative chemical durability. Specifically, when the alkali dissolution amount is measured according to the method of JIS R3502 (1995), the dissolution amounts of Li2O, Na2O, and K2O are preferably 2 mg or less, 1.8 mg or less, 1.6 mg or less, 1.4 mg or less, 1.2 mg or less, 1.0 mg or less, 0.8 mg or less, 0.6 mg or less, 0.4 mg or less, 0.2 mg or less, 0.1 mg or less, and 0.005 mg or less, respectively, and particularly preferably 0.003 mg or less. When the water resistance is low, ion exchange between alkali metals and protons on the surface of the glass is easy to proceed, and the part subjected to ion exchange is deteriorated and easily cracked.

[0118] The average surface roughness Ra of the main surface of the glass of the present invention is preferably less than 50nm, less than 25nm, less than 15nm, less than 10nm, less than 9nm, less than 8nm, less than 7nm, less than 6nm, less than 5nm, less than 4nm, less than 3nm, less than 2nm, and particularly preferably less than 1nm. When the surface roughness Ra is too large, light incident on the glass surface from the outside is easily scattered, and it is difficult for light to be emitted from the inside of the glass to the outside of the glass, and it is difficult to obtain the desired light transmittance. Moreover, the glass is easily broken. On the other hand, when the surface roughness Ra of the plane is too small, the glass surface is easily charged, and the attraction between the glass and the object contacting the glass surface becomes large, and it is sometimes difficult to obtain the desired demolding properties. Moreover, due to the charge on the glass surface, it is sometimes difficult to obtain the desired electrical responsiveness. In view of the above, the surface roughness Ra of the plane of the glass of the present invention is preferably more than 0.01nm, more than 0.03nm, more than 0.05nm, more than 0.07nm, more than 0.09nm, and particularly preferably more than 0.1nm.

[0119] The average surface roughness Ra of the end face of the glass of the present invention is preferably less than 100nm, less than 50nm, less than 25nm, less than 15nm, less than 10nm, less than 9nm, less than 8nm, less than 7nm, less than 6nm, less than 5nm, less than 4nm, less than 3nm, less than 2nm, and particularly preferably less than 1nm. When the surface roughness Ra of the end face is too large, it is difficult for light to enter the interior of the glass from the end face of the glass, and it is difficult for light to be emitted from the inside of the glass to the outside of the glass, and it is difficult to obtain the required light transmittance. And the glass is easily broken. On the other hand, if the surface roughness Ra of the end face is too small, when it is desired to physically support the glass through the end face of the glass, the contact area between the glass and the support body becomes smaller, or the frictional resistance becomes smaller, and it is difficult to support reliably. In view of the above situation, the surface roughness Ra of the end face of the glass of the present invention is preferably more than 0.01nm, more than 0.03nm, more than 0.05nm, more than 0.07nm, more than 0.09nm, and more than 0.1nm.

[0120] The glass of the present invention preferably has an unpolished surface. The theoretical strength of glass is originally very high, but in most cases, it will be broken under stress far below the theoretical strength. This is because, in the process after the glass is formed, such as the grinding process, small nano-scale defects called Griffith cracks are generated on the surface of the glass. Therefore, by making the surface of the glass of the present invention an unpolished surface, it is not easy to lose the original mechanical strength, and the glass is not easy to be broken. Moreover, since the grinding process can be omitted, the manufacturing cost can be reduced. In addition, for example, in the case where the glass of the present invention is plate-shaped, by making the effective surfaces of the two main surfaces as unpolished surfaces as a whole, the glass of the present invention is less likely to be broken. In addition, in order to make the effective surface as a whole an unpolished surface, it is more effective to make the part equivalent to the effective surface a free surface at the time of forming. Moreover, even if the part equivalent to the effective surface comes into contact with a solid component or the like during forming, the part in contact with the solid component or the like can be reheated at a temperature above the glass transition temperature after forming, thereby making a smooth surface similar to a free surface.

[0121] The waviness of the glass of the present invention is preferably 10 μm or less, 5 μm or less, 4 μm or less, 3 μm or less, 2 μm or less, 1 μm or less, 0.8 μm or less, 0.7 μm or less, 0.6 μm or less, 0.5 μm or less, 0.4 μm or less, 0.3 μm or less, 0.2 μm or less, 0.1 μm or less, 0.08 μm or less, 0.05 μm or less, 0.03 μm or less, 0.02 μm or less, and particularly preferably 0.01 μm or less. When the waviness is too large, the incident angle of the incident light incident from the glass surface at a specific position is easily distributed, and the light scattering amount on the glass surface becomes large after averaging, making it difficult to obtain the desired light transmittance. The lower limit of the waviness is not particularly limited, but is actually above 0.01 nm.

[0122] The thickness of the glass of the present invention is preferably 10 mm or less, 9 mm or less, 8 mm or less, 7 mm or less, 6 mm or less, 5 mm or less, and particularly preferably 4 mm or less. When the thickness of the sample is too thick, the attenuation rate of light inside the glass increases, and it is difficult to obtain the desired light transmittance. Moreover, when the glass of the present invention is used for display purposes, the thickness is preferably 1000 μm or less, 500 μm or less, 200 μm or less, 100 μm or less, 70 μm or less, 50 μm or less, 30 μm or less, 1 to 20 μm, and particularly preferably 5 to 10 μm.

[0123] The difference between the maximum thickness and the minimum thickness of the glass of the present invention is preferably 50 μm or less, 25 μm or less, 10 μm or less, 5 μm or less, 1 μm or less, 500 nm or less, 300 nm or less, 100 nm or less, 50 nm or less, 25 nm or less, 15 nm or less, 10 nm or less, 9 nm or less, 8 nm or less, 7 nm or less, 6 nm or less, 5 nm or less, 4 nm or less, 3 nm or less, 2 nm or less, and particularly preferably 1 nm or less. When the difference between the maximum thickness and the minimum thickness is too large, the incident angle of light incident from any direction of the front and back sides and the exit angle when emitted from the other side become different angles, and light is scattered unexpectedly, which easily becomes a glare appearance.

[0124] In addition, the surface roughness Ra of the main surface and the end surface of the glass can be measured according to the method of JIS B0601:2001. In addition, the waviness can be measured using a stylus-type surface shape measuring device in accordance with the method of SEMI STD D15-1296 "Method for measuring the surface waviness of FPD glass substrates". The thickness can be measured using a conventional device such as a digital vernier caliper or a point contact type roughness meter.

[0125] The glass of the present invention can also be chemically strengthened. The conditions of chemical strengthening treatment can consider the glass composition, the volume fraction of each phase, the type of molten salt, etc. and appropriately select the treatment time and treatment temperature. For example, it is also possible to select a glass composition containing more Na2O that can be contained in the residual glass phase, so as to easily perform chemical strengthening. In addition, the molten salt can contain monovalent cations such as Li, Na, K or divalent cations such as Mg, Ca, Sr, Ba, Zn, etc. alone, or it can contain multiple. Furthermore, not only conventional one-step strengthening can be selected, but also multi-step chemical strengthening can be selected. In addition, as molten salt, nitrates (potassium nitrate, sodium nitrate, lithium nitrate, etc.), carbonates (potassium carbonate, sodium carbonate, lithium carbonate, etc.), sulfates (potassium sulfate, sodium sulfate, lithium sulfate, etc.), chloride salts (potassium chloride, sodium chloride, lithium chloride, etc.) and combinations thereof can be used. Among them, as molten salt, it is preferred to use nitrates with low melting points, and sodium nitrate is particularly preferred. The ion exchange temperature is preferably 330 to 550° C., 350 to 500° C., and particularly preferably 390 to 450° C.; the ion exchange time is preferably 30 minutes to 12 hours, 45 minutes to 10 hours. In addition, the above-mentioned strengthening conditions can also be arbitrarily changed according to the desired use and strength, and the preferred conditions are not necessarily limited to the above-mentioned conditions.

[0126] When compressive stress is applied to the glass of the present invention by chemical strengthening, the compressive stress value (CS) is preferably 50 MPa or more, 100 MPa or more, 150 MPa or more, 200 MPa or more, 230 MPa or more, 260 MPa or more, and particularly preferably 300 MPa or more. If the compressive stress value is too small, Vickers hardness, bending strength, etc. may be reduced.

[0127] When compressive stress is applied to the glass of the present invention by chemical strengthening or the like, the compressive stress depth (DOC) is preferably 10 μm or more, 50 μm or more, 100 μm or more, 110 μm or more, and particularly preferably 120 μm or more. If the compressive stress depth is too small, the breaking strength may be reduced. In addition, the compressive stress value (CS) and the compressive stress depth (DOC) can be measured using a scattered light photoelastic stress meter SLP-1000 (manufactured by Orihara Seisakusho Co., Ltd.) and a surface stress meter FSM-6000 (manufactured by Orihara Seisakusho Co., Ltd.).

[0128] The damaged four-point bending strength of the glass of the present invention is preferably 150 MPa or more, 200 MPa or more, 235 MPa or more, 245 MPa or more, and particularly preferably 250 MPa or more. If the damaged four-point bending strength is too low, it is easy to break when dropped when used as a panel glass of a smartphone, etc. In addition, the upper limit of the damaged four-point bending strength is not particularly limited, and in reality it is 1500 MPa or less. In addition, the damaged four-point bending strength can be measured according to the following steps. First, while a glass plate processed to a thickness of 50 mm × 50 mm × 0.6 mm is made vertically, a 1.5 mm thick SUS plate is placed in close contact with the main surface of the glass plate and the opposite surface thereof to fix the glass plate. The front end of the pendulum-shaped arm is made to collide with sandpaper with a grit number of P180 to cause additional damage. The front end of the arm is The arm weight was 550 g. The arm was swung downward to a height of 5 mm from the collision point. The damaged glass plate was measured for four-point bending strength.

[0129] Furthermore, when the glass of the present invention is crystallized glass, it preferably has the same properties as described above.

[0130] The shape of the glass of the present invention is usually a plate shape (particularly a flat plate shape), but is not limited thereto and may be appropriately selected depending on the intended use.

[0131] Next, a method for producing the glass of the present invention will be described.

[0132] The method for producing glass of the present invention comprises: a step of melting glass raw materials to obtain molten glass; and a step of shaping the molten glass.

[0133] Specifically, first, a raw material batch (glass raw material) prepared in a manner to form a glass of the above composition is put into a glass melting furnace, melted at a temperature of 1200 to 1800° C., and molten glass is obtained, and then formed. When melting the glass, any one of the melting methods of a flame melting method using a burner, an electric melting method using electric heating, a melting method using laser irradiation, a melting method using plasma, a liquid phase synthesis method, and a gas phase synthesis method or a combination of two or more methods can be used.

[0134] The forming method is preferably selected from at least one of overflow method, floating method, downdraw method, orifice downdraw method, redraw method, containerless method, blowing method, pressing method, roller pressing method, bushing method and tube drawing method. In addition, reheating at a temperature above the glass transition temperature can be performed after forming. In this way, the glass of the present invention with good surface quality can be manufactured.

[0135] When forming by overflow method, the viscosity of the glass at the lower top portion of the grooved refractory is preferably 10 3.5 ~10 5.0 dPa·s. As long as the lower top portion of the grooved structure is not subjected to any force, the glass will shrink and fall downward under the action of surface tension. In order to prevent this, it is necessary to clamp the two sides of the glass blank with rollers and stretch it in the width direction to prevent the glass blank from shrinking. When the glass of the present invention is formed, since the heat contained in the glass itself is small, the cooling rate of the glass is rapidly accelerated at the moment of leaving the grooved refractory. Therefore, the viscosity of the glass at the lower top portion of the grooved refractory is preferably 10 5.0 dPa·s or less, 10 4.8 dPa·s or less, 10 4.6 dPa·s or less, 10 4.4 dPa·s or less, 10 4.2 dPa·s or less, particularly preferably 10 4.0 By doing so, when tensile stress is applied in the width direction, it is possible to prevent breakage, increase the plate width, and stably extend downward.

[0136] Next, the obtained glass is annealed. The main purpose of annealing is to remove strain and residual stress. In this case, it is preferred to heat treat in a temperature range of room temperature to strain point (≈ glass transition temperature -5 to -20°C) for at least 1 minute, more preferably 3 minutes, 16 minutes, and most preferably more than 30 minutes. In this way, it is easy to obtain glass consisting of only a single glass phase, and as a result, the chemical durability of the glass can be improved, the surface of the glass can be easily controlled, and the desired light transmittance can be easily obtained. On the other hand, annealing can also be used to eliminate strain and residual stress while forming phase separation in the glass. In this case, it is preferred to heat treat in a temperature range higher than the strain point for at least 1 minute, more preferably 3 minutes, 16 minutes, and most preferably more than 30 minutes. In this way, the glass can be phase-separated, and its phase separation state is binocular phase separation in most cases. In addition, when the glass of the present invention is phase-separated, it is divided into a first phase containing more SiO2 and a second phase and subsequent phases other than this. In most cases, the chemical durability of the second phase and subsequent phases is lower than that of the first phase. In this case, due to the difference in chemical durability of each phase, it is easy to form unevenness on the glass surface, but by designing the appropriate glass composition as described above, the state of the unevenness can be controlled to a degree that can obtain the desired light transmittance. In addition, by giving fine unevenness, not only can the demolding property of the glass of the present invention and the object in contact with the glass of the present invention be improved, but also the surface area of ​​the glass surface is made larger than the free surface state, thereby increasing the friction force, improving the physical and chemical adsorption force, and realizing the high functionality of the glass of the present invention. In addition, annealing can also be performed in the state of applying and irradiating sound waves or electromagnetic waves.

[0137] In addition, as described above, when the glass of the present invention is used as a cooking top plate and a white or milky white appearance is required, it is preferably phase-separated into two or more phases. In order to obtain glass with the white or milky white appearance, it is preferred to heat-treat the formed glass of the present invention by staying in a temperature range higher than the strain point for at least 1 minute. Specifically, the temperature for heat treatment is preferably 700°C or more, 800°C or more, 850°C or more, particularly preferably 900°C or more, preferably 1500°C or less, 1200°C or less, 1100°C or less. When the temperature for heat treatment is too high, the glass changes from a solid state to a molten liquid state, and it is difficult to obtain the desired shape. On the other hand, when the temperature for heat treatment is too low, it is difficult to efficiently separate the phases, resulting in an increase in manufacturing costs. The time for heat treatment is preferably 1 minute or more, 1 hour or more, 5 hours or more, 10 hours or more, 20 hours or more, particularly preferably 24 hours or more, preferably 1000 hours or less, 500 hours or less, 100 hours or less, 50 hours or less. When the time for heat treatment is outside the above range, it is difficult to obtain glass with the desired properties.

[0138] Furthermore, the cooling rate when cooling the glass of the present invention which has reached a high temperature can be set to a specific temperature gradient or a temperature gradient of two or more levels. In the case of obtaining sufficient thermal shock resistance, it is preferred to control the cooling rate so that the structural relaxation of the residual glass phase is fully carried out. In this case, the average cooling rate from the highest annealing temperature to 25°C is preferably 3000°C / min, 1000°C / min or less, 500°C / min or less, 400°C / min or less, 300°C / min or less, 200°C / min or less, 100°C / min or less, 50°C / min or less, 25°C / min or less, 10°C / min or less, and particularly preferably 5°C / min or less. In addition, in the case of obtaining long-term dimensional stability, it is further preferred to be 2.5°C / min or less, 1°C / min or less, 0.5°C / min or less, 0.1°C / min or less, 0.05°C / min or less, and particularly preferably 0.01°C / min or less. Except for the case where a physical strengthening treatment such as air cooling or water cooling is performed, the cooling rate of the low thermal expansion glass is preferably close to the cooling rate of the glass surface and the cooling rate of the inner wall thickness farthest from the glass surface. The value obtained by dividing the cooling rate of the inner part of the glass farthest from the surface by the cooling rate of the surface is preferably 0.0001-1, 0.001-1, 0.01-1, 0.1-1, 0.5-1, 0.8-1, 0.9-1, and particularly preferably 1. When it is close to 1, residual strain is not easily generated at all positions of the glass of the present invention, and long-term dimensional stability is easily obtained. In addition, the cooling rate of the surface can be estimated using a contact temperature measurement or a radiation thermometer. The temperature inside the glass can be estimated based on numerical data obtained by immersing the low thermal expansion glass in a high temperature state in a cooling medium and measuring the heat and heat change rate of the cooling medium, the specific heat of the low thermal expansion glass and the cooling medium, and the thermal conductivity.

[0139] The obtained glass of the present invention may be cut. For example, when cutting is performed using a wire saw, it is preferable to cut the glass while supplying a slurry containing a grinding abrasive to the wire saw.

[0140] The method may further include the step of heat-treating the glass obtained by the step of shaping the molten glass to crystallize the glass.

[0141] Specifically, by heat treating the annealed glass to crystallize it, crystallized glass can be obtained. The crystallization conditions are as follows. First, at a temperature of 700°C to 1200°C (preferably 750 to 900°C), a crystal nucleus is formed for 0.1 to 60 hours (preferably 0.25 to 50 hours, more preferably 1 to 40 hours), followed by a crystal growth for 0.1 to 50 hours (preferably 0.2 to 10 hours, more preferably 0.25 to 5 hours) at a temperature of 800 to 1300°C (preferably 850 to 1100°C). In addition, the heat treatment in each process of crystal nucleus formation and crystal growth can be performed only at a certain specific temperature, or heat treatment can be performed in stages at a temperature maintained at more than two levels, or heating can be performed in a state where a temperature gradient is applied. In addition, it is also possible to heat treat only crystal growth without performing crystal nucleus formation. In this way, a crystallized glass, such as the following crystals, can be obtained. Specifically, ZnAl2O4 (zinc spinel), willemite (zinc silicate), Al2SiO5 (aluminum silicate), zirconium oxide, zirconium titanate, tin-containing zirconium oxide, titanium oxide, aluminum titanate, β-quartz solid solution, α-quartz, β-quartz, β-spodumene solid solution, spodumene, zircon, cordierite, enstatite, mica, nepheline, anorthite, lithium disilicate, lithium metasilicate, wollastonite, diopside, cristobalite, tridymite, feldspar, spinel crystals, metal colloids, etc. In addition, these crystals may contain only one or more.

[0142] In addition, crystallization can be precipitated by annealing, and crystallization can also be promoted by applying and irradiating sound waves or electromagnetic waves. And the cooling rate when the crystallized glass of the present invention reaching high temperature is cooled can be set to a specific temperature gradient or to a temperature gradient above two levels. The cooling rate is preferably the same as the cooling rate of the above-mentioned glass.

[0143] Example

[0144] The present invention is described below based on examples, but the present invention is not limited to the following examples. Tables 1 to 6, 14 to 16 show the composition of the glass (amorphous glass before crystallization) of the examples of the present invention (samples No. 1 to 36, 41 to 58), Tables 7 to 12, 17 to 19 show the characteristic values ​​of each glass in Tables 1 to 6, 14 to 16, Table 13 shows the characteristic values ​​of crystallized glass No. 37 to 40 obtained by heat treating each glass No. 1 to 4 in Table 1, and Table 20 shows the characteristic values ​​of glass obtained by heat treating No. 55 in Table 16.

[0145] [Table 1]

[0146]

[0147] [Table 2]

[0148]

[0149] [Table 3]

[0150]

[0151] [Table 4]

[0152]

[0153] [Table 5]

[0154]

[0155] [Table 6]

[0156]

[0157] [Table 7]

[0158]

[0159] [Table 8]

[0160]

[0161] [Table 9]

[0162]

[0163] [Table 10]

[0164]

[0165] [Table 11]

[0166]

[0167] [Table 12]

[0168]

[0169] [Table 13]

[0170]

[0171] [Table 14]

[0172]

[0173] [Table 15]

[0174]

[0175] [Table 16]

[0176]

[0177] [Table 17]

[0178]

[0179] [Table 18]

[0180]

[0181] [Table 19]

[0182]

[0183] [Table 20]

[0184]

[0185] First, each raw material is prepared in the form of oxides, hydroxides, carbonates, nitrates, etc. to form a glass having the composition described in each table, and a glass batch is obtained (the composition described in Tables 1 to 6, 14 to 16 is the analysis value of the glass actually produced. The analysis is carried out by a scanning fluorescent X-ray analyzer ZSX series manufactured by RIGAKU. In the table, regarding the sum of each component and the ratio of each component, the oxygen element and the coefficient are omitted and marked as, for example, "Li+Na+K", etc.). After the obtained glass batch is melted at a temperature of 1200 to 1800°C for 0.5 to 400 hours, the obtained molten glass is rolled by a roller pressing method while cooling it to form a glass with a width of 100 mm and a thickness of 5 mm. Then, a slow cooling kiln is used to perform heat treatment at a temperature of -150 to -50°C, the glass transition temperature, for 30 minutes, and the slow cooling kiln is cooled to room temperature at -100°C / h, thereby obtaining glasses No. 1 to 36 and 41 to 58.

[0186] Glasses No. 1 to 4 described in Table 1 were heat treated to crystallize under the conditions described in Table 13. They were then heat treated at 700° C. for 30 minutes and cooled to room temperature at −100° C. / h to obtain crystallized glasses No. 37 to 40.

[0187] The glass batch material of composition No. 55 recorded in Table 16 was formed by the same method as above, and then heat treated at 950°C for 24 hours in a slow cooling kiln, and the slow cooling kiln was cooled to room temperature at -100°C / h, thereby obtaining glass No. 59 recorded in Table 20.

[0188] The prepared glass samples were processed by physical grinding, chemical grinding, chemical etching, flame blasting, etc., and evaluation samples for β-OH value, viscosity, liquidus temperature, liquidus viscosity, density, linear thermal expansion coefficient, Young's modulus, rigidity modulus, Poisson's ratio, etc. were prepared and evaluated. In addition, the obtained molten glass was formed into a length of 400 mm by the overflow method, and heat-treated at a temperature of -150 to -50°C, the glass transition temperature, for 30 minutes using a slow cooling kiln, and the slow cooling kiln was cooled to room temperature at -100°C / h to obtain a glass plate. The surface roughness Ra of the main surface of the obtained glass plate, the surface roughness Ra of the end surface, and the waviness were measured.

[0189] The Pt and Rh contents of the prepared samples were analyzed using an ICP-MS device (Agilent 8800 manufactured by Agilent Technologies) in the following manner. First, the prepared glass sample was crushed and moistened with pure water, and then perchloric acid, nitric acid, sulfuric acid, hydrofluoric acid, etc. were added and melted. Then, the Pt and Rh contents of the sample were measured by ICP-MS (inductively coupled plasma mass spectrometry). In addition, based on the calibration curve prepared using the Pt and Rh solutions with known concentrations prepared in advance, the Pt and Rh contents of each measured sample were calculated. The measurement mode was set to Pt: He gas / HMI (low mode) and Rh: HEHe gas / HMI (medium mode), and the mass number was set to Pt: 198 and Rh: 103. In addition, the Li2O content of the prepared sample was analyzed using an atomic absorption spectrometer (ContrAA600 manufactured by Analytik Jena). The melting procedure of the glass sample and the use of the calibration curve are basically the same as those for the Pt and Rh analysis. In addition, other components are measured by ICP-MS or atomic absorption analysis in the same way as Pt, Rh, and Li2O. Alternatively, a glass sample with a known concentration previously analyzed by an ICP-MS or atomic absorption analysis device is used as a calibration curve sample, and a calibration curve is prepared using an XRF (fluorescent X-ray) analysis device (ZSX Primus IV manufactured by RIGAKU). Then, based on the calibration curve, the actual content of each component is obtained from the XRF analysis value of the measured sample. When performing XRF analysis, the tube voltage, tube current, exposure time, etc. are adjusted at any time according to the analyzed component.

[0190] The β-OH value was determined by measuring the light transmittance of the glass using an infrared spectrophotometer (FT-IR Frontier manufactured by PerkinElmer) and using the following formula. The scanning speed was set to 100 μm / min and the sampling interval was set to 1 cm. ﹣1 The number of scans was set to 10 for each measurement.

[0191] β-OH value = (1 / X)log(T1 / T2)

[0192] X: Glass thickness

[0193] T1: Reference wave number 3846cm ﹣1 The light transmittance

[0194] T2: OH group absorption wave number 3600cm ﹣1 Minimum light transmittance near

[0195] The linear thermal expansion coefficient is obtained by using The average linear thermal expansion coefficient of the sample measured in the temperature range of 30 to 380°C and 30 to 750°C was evaluated. The measurement was performed using a Dilatometer manufactured by NETZSCH. In addition, the thermal expansion curve of the glass sample in the temperature range of 30 to 750°C was measured using the same measuring instrument, and its inflection point was calculated to evaluate the glass transition temperature and yield point.

[0196] A sample with a thickness of 4 mm and a surface roughness equivalent to that of optical polishing was used to evaluate the transmittance, brightness and chromaticity using a spectrophotometer. A spectrophotometer V-670 manufactured by JASCO Corporation was used for the measurement. In addition, the V-670 is equipped with "ISN-723" as an integrating sphere unit, and the measured transmittance is equivalent to the total light transmittance. In addition, the measurement wavelength range is set to 200 to 2500 nm, the scanning speed is set to 200 nm / minute, the sampling interval is set to 1 nm, the bandwidth is 5 nm in the wavelength range of 200 to 800 nm, and 20 nm in the other wavelength ranges. Baseline correction (100% match) and dark area measurement (0% match) were performed before the measurement. When measuring the dark area, the barium sulfate plate attached to the ISN-723 was removed. Using the measured light transmittance, tristimulus values ​​XYZ were calculated based on JIS Z8781-42013 and international standards corresponding thereto, and lightness and chromaticity (illuminant C / 10°) were calculated from each stimulus value.

[0197] The Young's modulus, rigidity modulus and Poisson's ratio of a plate-shaped sample (40 mm × 20 mm × 20 mm) after the surface was polished with a polishing liquid in which No. 1200 alumina powder was dispersed were measured at room temperature using a free resonance elastic modulus measuring device (Nihon Techno-Plus JE-RT3). In addition, the specific elastic modulus was calculated by dividing the obtained Young's modulus by the density.

[0198] The density was evaluated by the Archimedean method.

[0199] The high temperature viscosity is evaluated by the platinum ball pulling method as follows. The bulk glass sample is broken into appropriate sizes and placed in an alumina crucible. The alumina crucible is then heated to make the sample a molten liquid. The viscosity of the glass at various temperatures is measured, the constant of the Vogel-Fulcher formula is calculated, and a viscosity curve is prepared to calculate the viscosity (10 4 dPa·s, 10 3.5 dPa·s, 10 3 dPa·s, 10 2.5 dPa·s and 10 2 dPa·s) under temperature.

[0200] The liquidus temperature is evaluated by the following method. First, fill a glass powder shaped into 300 to 500 μm in a platinum boat of about 120×20×10 mm, put it into an electric furnace, and melt it at a temperature of 1400 to 1800°C for 30 minutes. Then, move the platinum boat to an electric furnace with a linear temperature gradient and keep it for 20 hours to precipitate the devitrified product. Cool the measured sample to room temperature with air, and then observe the devitrified product precipitated at the interface between the platinum boat and the glass. Calculate the temperature of the devitrified precipitation site based on the temperature gradient curve of the electric furnace as the liquidus temperature. In addition, the obtained liquidus temperature is interpolated into the high-temperature viscosity curve of the glass, and the viscosity matching the liquidus temperature is evaluated as the liquidus viscosity.

[0201] The dielectric constant, dielectric loss tangent, and low-temperature volume resistivity of a plate-shaped sample (50 mm×50 mm×3 mm) whose surface was polished with a polishing liquid containing No. 1200 alumina powder were measured using an impedance analyzer at room temperature at a frequency of 1 MHz.

[0202] The surface roughness Ra of the main surface and the end surface of the glass was measured according to the method of JIS B0601:2001.

[0203] The waviness is a measured value of WCA (filter centerline waviness) described in JIS B0601:2001 measured using a stylus-type surface profile measuring device. The measurement is performed in accordance with the method of SEMIST D15-1296 "Measurement method for surface waviness of FPD glass substrates". The cutoff value during the measurement is set to 0.8 to 8 mm, and the measurement is performed in a direction perpendicular to the rolling direction of the glass during molding with a length of 300 mm.

[0204] Most of the glasses of Examples No. 1 to 59 of the present invention are materials with a small linear thermal expansion coefficient and high heat resistance and thermal shock resistance. In particular, No. 1 to 36, 41, 43 to 44, 48 to 49 have high colorless transparency. In addition, No. 42, 45 to 47, 50 to 58 are colored in brown, ultramarine to black, etc. In addition, it was confirmed that the glass of No. 59 was phase-separated into two or more phases, and the appearance was milky white.

[0205] Industrial Applicability

[0206] The ZnO-Al2O3-SiO2 glass of the present invention is preferably used for a cooker top plate, fireproof window, heat-resistant tableware or building materials. Specifically, the glass of the present invention is suitable as a substrate for high-tech products such as a front window of an oil stove, a wood stove, a color filter or an image sensor substrate, a fixture for firing electronic parts, a diffuser, a furnace core tube for semiconductor manufacturing, a mask for semiconductor manufacturing, an optical lens, a size measurement component, a communication component, a building material, a chemical reaction container, an electromagnetic cooking top plate, heat-resistant tableware, a heat-resistant cover, a window glass for a fireproof door, a component for an astronomical telescope, a component for cosmic optics, a coloring material, a light-absorbing material, a temperature regulating material, a soundproofing material, a dielectric component, a linear thermal expansion coefficient regulating material, a battery component, a resin or the like strength improvement component, a display component, a chemical strengthening material, etc. In addition, when the ZnO-Al2O3-SiO2 system glass of the present invention is a crystallized glass, it is preferably used for a cooker top plate, a fireproof window, heat-resistant tableware or building materials. In addition, the use of the ZnO-Al2O3-SiO2 glass of the present invention is not limited to the above uses. In addition, it can be used for the above uses alone or in combination with the above uses. As a combination example, an electromagnetic cooking top plate with a display function, or a smart phone with a display screen subjected to a chemical strengthening treatment, etc. can be cited.

Claims

1. A ZnO-Al2O3-SiO2 glass, characterized in that: In terms of mass %, it contains 40 to 90% of SiO2, 5 to 35% of Al2O3, more than 0% and less than 35% of ZnO, and 0 to 5% of Li2O+Na2O+K2O.

2. The ZnO-Al2O3-SiO2 glass according to claim 1, characterized in that: In terms of mass %, it contains more than 0% Fe2O3.

3. The ZnO-Al2O3-SiO2 glass according to claim 1, characterized in that: In terms of mass %, it contains less than 10% HfO2.

4. The ZnO-Al2O3-SiO2 glass according to claim 1, characterized in that: Contains less than 30 ppm of Pt and less than 30 ppm of Rh.

5. The ZnO-Al2O3-SiO2 glass according to claim 1, characterized in that: In terms of mass %, it contains more than 0% of MoO3.

6. The ZnO-Al2O3-SiO2 glass according to claim 1, characterized in that: In terms of mass %, it contains more than 0% SnO2.

7. The ZnO-Al2O3-SiO2 glass according to claim 1, characterized in that: In terms of mass %, it contains more than 0% Cr2O3.

8. The ZnO-Al2O3-SiO2 glass according to claim 1, characterized in that: In terms of mass ratio, Al2O3 / ZnO is 0.14-2300.

9. The ZnO-Al2O3-SiO2 glass according to claim 1, characterized in that: In terms of mass ratio, ZnO / (SiO2+B2O3) exceeds 0 and is equal to or less than 0.

75.

10. The ZnO-Al2O3-SiO2 glass according to claim 1, characterized in that: In terms of mass ratio, (Li2O+Na2O+K2O) / Fe2O3 is less than 10,000.

11. The ZnO-Al2O3-SiO2 glass according to claim 1, characterized in that: In terms of mass %, ZnO+B2O3+P2O5 exceeds 0% and is 55% or less.

12. The ZnO-Al2O3-SiO2 glass according to claim 1, characterized in that: In terms of mass ratio, (ZnO+B2O3+P2O5) / ZnO is greater than 1.

001.

13. The ZnO-Al2O3-SiO2 glass according to claim 1, characterized in that: The linear thermal expansion coefficient at 30-750°C is 60×10 ﹣7 / ℃ below.

14. The ZnO-Al2O3-SiO2 glass according to claim 1, characterized in that: The light transmittance at a thickness of 4 mm and a wavelength of 555 nm is above 0.1%.

15. The ZnO-Al2O3-SiO2 glass according to claim 1, characterized in that: The Young's modulus is 65 GPa or more.

16. The ZnO-Al2O3-SiO2 glass according to any one of claims 1 to 15, characterized in that: The glass is crystallized glass.

17. A method for producing ZnO-Al2O3-SiO2 glass, used for producing the glass according to any one of claims 1 to 15, wherein the method is characterized in that: include: The steps of melting glass raw materials to obtain molten glass; and shaping the molten glass. The method for shaping the molten glass is at least one selected from overflow method, float method, down-draw method, orifice down-draw method, re-draw method, containerless method, blowing method, pressing method, rolling method, bushing method and tube drawing method.

18. The method for producing a ZnO-Al2O3-SiO2 glass according to claim 17, wherein: The method further includes the step of heat treating the glass obtained by the step of shaping the molten glass to crystallize the glass.

19. The ZnO-Al2O3-SiO2 glass according to any one of claims 1 to 15, characterized in that: The glass is used for a cooker top plate, a fireproof window, a heat-resistant tableware or a building material.

20. The ZnO-Al2O3-SiO2 glass according to claim 16, characterized in that: The glass is used for a top plate for a cooker, a fireproof window, a heat-resistant tableware or a building material.

Citation Information

Patent Citations

  • Li2o-al2o3-sio2-based transparent crystallized glass for combustion apparatus window

    JP1989308845A